Dietary Coenzyme Q10 improves salinity adaptation in Nile tilapia (Oreochromis niloticus) through coordinated energy metabolism and redox homeostasis - Jinquan Fan; Jia Li; Yuxi Yan; Zijuan Cheng; Erchao Li; Liqiao Chen; Xiaodan Wang (Aquaculture, 2027)

Multiscale investigation of the structure, interaction mechanism, and physicochemical properties of α-lactalbumin and soybean lecithin complexes: integrating spectroscopy, molecular dynamics, and density functional theory - Yuanyuan Li; Ning Guan; Haifu Jia; Yougui Cheng; Xiaoyan Pei; Biao Liu; Jingzhou Xiao; Yujun Jiang; Qianyu Zhao; Ling Guo (Food Hydrocolloids, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Seasonally driven ecological adaptation in sea cucumbers Apostichopus japonicus: dynamic coupling of nutrient metabolism and gut microbial network reconfiguration - Ping Li; Jia-Ming Zhang; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Reviews in Fish Biology and Fisheries, 2026)

Postoperative wound microenvironment regulates breast cancer stem cell fate and clinical implications - Cheng Yang; Zhongjian Wen; Xiaoqin Huang; Yali Yang; Jia Zhang; Yunfei Li; Yiren Wang; Yuxin Zhong (Molecular Biology Reports, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Identification of the BrSK gene family in flowering Chinese cabbage and functional characterization of BrSK2 subfamily involvement in heat stress - Haobo Yang; Kehang Chen; Rahat Sharif; Haosen Wang; Xinqing Zhao; Cheng Zhang; Jia Li; Yudan Wang (Plant Science, 2026)

The tree-ring δ18O network over Northeast China captures regional climate variability: coherence, gradients, and site-dependent controls - Qiang Li; Jiachuan Wang; Yu Liu; Chenxi Xu; Takeshi Nakatsuka; Yifan Wu; Zichun Jia; Yang Xu; Changfeng Sun; Huiming Song; Qiufang Cai; Meng Ren; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Discovery of a novel microcystin-producing Snowella (Chroococcales, Cyanobacteria) from the Qinghai-Tibet Plateau: expanding the diversity of cyanotoxin source origins in aquatic ecosystems - Yao Cheng; Yilang Wang; Peng Xiao; Nannan Jia; He Zhang; Youxin Chen; Gongliang Yu; Yawen Fan; Renhui Li (Harmful Algae, 2026)

Elucidating dynamic migration mechanism of oxygen species in lanthanum oxide catalytic oxidative coupling of methane reaction based on developed deep potential function - Yurong Liu; Yuhao Wang; Zijie Cheng; Bingying Han; Riguang Zhang; Lixia Ling; Pengyu Niu; Litao Jia; Maohong Fan; Xiangyuan Li; Xianxian Hu; Baojun Wang (Fuel, 2026)

Shape-finding for a triple-tower spatial double-cable suspension bridge with upper hangers - Wei Liu; Li Zhu; Xue-Jin Huo; Xiao-Wei Ma; Jia-Huan Li; Xu-Xu Cheng (Engineering Structures, 2026)

Performance evaluation of fan-driven air ventilation garments for personal cooling using a coupled human thermoregulation–heat and moisture transport model - Jie Jia; Zhenyang Li; Jing Wang; Xinyu Jia; Hongwei Liu; Jiahui Cheng (Energy and Buildings, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

A proximity-allosteric Adapter unlocks Cas12a exponential amplification for versatile homogeneous assay - Feiyu Chen; Man Tang; Zhangling Liu; Wuxian Li; Xingping Hu; Linguo Xiang; Lanxin Jiang; Yanna Ban; Jing Wang; Jia Li; Wei Cheng; Tiantian Yang (Analytica Chimica Acta, 2026)

Aggregation-induced dual-emission carbon dots for visual discrimination of methanol from ethanol - Hui-Shuang Li; Cheng-Feng Zhang; Li-Jia Liu; Hong-Wei Li; Fuquan Bai; Yuqing Wu (Analytica Chimica Acta, 2026)

Plastic fragments impair soil organic carbon persistence through reshaping microbial metabolism and decreasing plant carbon supply in dryland ecosystems - Meng-Ying Li; Wei Wang; Yudi M. Lozano; Jia-Yao Yang; Yue Ma; Xiao-Bin Xiong; Shuang-Jin Huang; Muhammad Ashraf; Jian-Ming Li; Yun-Li Xiao; Zheng-Guo Cheng; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Cobalt-doped cotton-derived carbon for enhancing the performance of antimony-removing microbial electrolysis cells - Leyi Chen; Haowen He; Jiayuan Huang; Haifeng Cheng; Chengjun Guo; Xing Chen; Xing Lu; Kengqiang Zhong; Jingyi Wang; Jiaqian Zhang; Meng Li; Lei Huang; et al. (Journal of Water Process Engineering, 2026)

AI-assisted multimodal spectral fusion for quantitative analysis of quinolone antibiotics in pharmaceutical wastewater - Cheng Peng; Jia Li; Hengchang Zang (Journal of Environmental Chemical Engineering, 2026)

A mitochondria-targeted fluorescent probe for monitoring of H2O2 and polarity/viscosity-related microenvironmental changes in food mycotoxin- and environmental contaminant-induced hepatotoxicity - Zibo Zhai; Jia Huang; Xijian Wang; Hailin Zhang; Min Deng; Qiqi Wen; Jingting Fang; Lizi Liu; Ziyang Ding; Dan Cheng; Longwei He; Songjiao Li (Journal of Environmental Chemical Engineering, 2026)

The critical role of electrode spacing in constructed wetland-microbial fuel cell system: A review of the last fifteen years’ literature - Bin Ji; Chengyuan Jia; Chenglin Liu; Xiuping Sun; Cheng Shen; Huarui Li; Yaqian Zhao (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Sedimentological and reservoir characteristics of Carboniferous–Permian shales in the northern Songliao Basin and surrounding areas, Northeastern China - Honggang Cheng; Deyong Li; Xuefeng Bai; Lin Jiang; Qinghua Huang; Dehai Wang; Hui Wang; Shujuan Xu; Xueqiong Wu; Wei Duan; Chengzao Jia (Journal of Asian Earth Sciences, 2026)

Spatiotemporal dynamics of global vegetation growth synchrony: Analysis from complex network - Fang Wu; Junwen Jia; Cheng Li; Xuefeng Cui (Global and Planetary Change, 2026)

Constructing a Cu: MoO3/g-C3N4 heterostructure with broad visible-light response to enhance CO2-to-methanol conversion performance - RuoKun Jia; TianXiang Li; PengPeng Wang; DuMin Li; JiaHui Chen; XiaoHang Yang; QingXiao Zhao; Xin Cheng; LingYun Zhang; Xiaoxi Liu (Fuel, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

Interfacial electronic regulation of copper-modified manganese dioxide electrode and mechanism of electrocatalytic degradation of minocycline - Jia Li; Jian Zhang; Jiayi Liu; Haina Bai; Xin Cheng; Ruoyi Li (Chemical Engineering Journal, 2026)

Atomic-scale Cu in situ confined in ZIF-8 as a chemical-biomolecular bridge for visible-light-activated therapy of Staphylococcus aureus biofilm-associated skin infections - Xuehua Chen; Tai-Cheng Zhou; Hao Wang; Xilun Wang; Zhiguo Zhu; Changle Wen; Xiaoxiao Shi; Hanglin Li; Yang Tang; Jia Wei (Chemical Engineering Journal, 2026)

Indium selenide framework constructed from supertetrahedral clusters for efficient adsorption of Cs+ and Sr2+ - Fei-Fei Wang; Yu-Hang Li; Ze-Jia Shen; Ze-Yu Wang; Lin Cheng; Shuaihua Wang; Kai-Yao Wang (Chemical Engineering Journal, 2026)

CRISPR/enzyme cascade-driven transistor overcomes Debye screening for culture-free detection of resistant bacteria - Jiahao Li; Min Jia; Han Liu; Weini Xin; Zhi-Yong Zhang; Chen-Zhong Li; Guo-Jun Zhang; Cheng Jiang (Chemical Engineering Journal, 2026)

Forchlorfenuron (CPPU) suppresses fruitlet abscission in Areca catechu by modulating carbohydrate allocation, hormonal dynamics, and lignin biosynthesis - Lin-Kai Wang; Wen-Cheng Fan; Han Gong; Dong-Xia Li; Li-Yun Liu; Meng Li; Jia Li (Planta, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Making Waves: Emerging Risks as Regulatory Mismatch Meets Automation in LLM-Agents like OpenClaw for Water Treatment and Environmental Infrastructure - Yu-Qi Wang; Boyan Xu; Hao-Lin Yang; Jia-Ji Chen; He-Wen Li; Wen-Zhe Wang; Hong-Cheng Wang (Water Research, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Characteristics and potential formation mechanisms of dissolved organic matter at the water-sediment interface and assessment of its release potential in the eastern pacific polymetallic nodule area - Yuanhao Zhang; Zhidan Liu; Li Zou; Cheng Wu; Xueqing Zhang; Haibing Ding; Yongzheng Quan; Yonggang Jia (Water Research, 2026)

Tracking the first arrival in Asia: Early Eocene Thuja (Cupressaceae) from Lingbao, Henan, central China - Wei Wang; Qijia Li; Hui Jia; Congyi Wu; Cheng Quan (Review of Palaeobotany and Palynology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Orchestrating immunity and beyond: polysaccharides as multi-target regulators of inflammatory networks via gut microbiota and structure-dependent pathways - Hao Cheng; Jing Wen; Qingyao Jia; Lijun Luo; Yong Li; Xing Wang; Shiyu Yang; Xingyue Su; Yijun Zhang; Shenglan Li; Wuwen Feng; Cheng Peng (Food Research International, 2026)

Zearalenone-induced hepatotoxicity: Underlying mechanisms and genistein-mediated preventive effects - Ruo Du; Qingyuan Li; Yi Cheng; Yuting Zeng; Mairewulan Abula; Wenyi Liu; Fangfang Yu; Weihua Jia; Yuhui Du; Yue Ba; Yanjie Wang; Guoyu Zhou (Food and Chemical Toxicology, 2026)

Study on the mechanism of synergistic adsorption of CO2 and Hg0 by Mg-MOF-74-derived modified composites based on experiment and density functional theory - Peng Cheng; Li Jia; Jia-hao Zhao; Ya-wen Wu; Yue Yu; Xiao-fang Gao; Qing Meng; Yan Jin (Chemical Engineering Journal, 2026)

Oral sunflower pollen-derived biomimetic delivery system for combined chemoimmunotherapy of colorectal cancer - Xin-Yue Xu; Meng Guan; Kai Cheng; Yong-Guo Hu; Li-Li Chen; Zi-Hui Yan; Jie Xiong; Dong Zhou; Jia-Hua Zou; Jin-Xuan Fan; Yuan-Di Zhao; Xiao-Shuai Zhang (Chemical Engineering Journal, 2026)

Desorption hysteresis controlled gas migration and apparent permeability evolution in gas-bearing coal under thermo-hydro-mechanical coupling - Zhonghui Wang; Shoujian Peng; Jiang Xu; Jiaxuan Chen; Li Jia; Liang Cheng; Qixian Li; Jiajia Liu (Chemical Engineering Journal, 2026)

Variation trend and source analysis of ·OH in atmosphere through probe capturing method: A case study during winter at a mountain observation site - Zhiqi Kang; Shiming Jia; Jiaxian Li; Tiantian Wang; Yang Yang; Shuai Liang; Guanghui Cheng; Xin Li; Gaofeng Shi; Guoying Wang (Atmospheric Pollution Research, 2026)

Lacticaseibacillus rhamnosus GR-1 Alleviates Escherichia coli-induced Autophagy-dependent Ferroptosis in Bovine Endometrial Epithelial Cells via FOXO1 Signaling - Xiangfu Wen; Mengsen Wang; Deyuan Song; Xiaohan Li; Meiyi Ren; Jinshang Song; Guowei Liang; Jing Chang; Ziyan Wang; Hao Li; Jia Cheng; Mingchao Liu (Probiotics and Antimicrobial Proteins, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Investigating the Antiviral Mechanism of Kaempferol Against Grouper Iridovirus: Combined Evaluation of In Vitro Activity and In Vivo Efficacy - Nijia Xue; Lin Huang; Jieying Yu; Jia Cai; Zhengzhao Liu; Yibing Wang; Shu Cheng; Junxiang Lai; Ying Pan; Qing Yu; Wenhong Li; Pengfei Li (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is one of the major pathogens that pose significant threats to the aquaculture industry. Kaempferol is a flavonoid compound extracted from Illicium verum Hook.f. (star anise), a material that is both edible and used in traditional medicine. In this study, we evaluated the antiviral effects of kaempferol against SGIV in vitro and in vivo, and elucidated the antiviral mechanism. Our study found that kaempferol could effectively resist SGIV infection in vitro and in vivo. Kaempferol might destroy the SGIV envelope and interfere with the attachment, invasion, and replication stages of SGIV infection. Transcriptomic analysis showed that differentially expressed genes regulated by kaempferol were enriched in ribosome, NF‐κB, and phospholipase D signalling pathways. Further screening of immunity‐related genes and pathway analysis revealed that antiviral immune responses were mainly governed by the JAK–STAT, PI3K‐Akt, and TNF signalling pathways. This study demonstrated that kaempferol exhibited significant antiviral effects against SGIV through multiple mechanisms and had the potential to become an anti‐SGIV fishery drug. These findings provide a theoretical basis for the development of effective drugs for the prevention and treatment of SGIV.

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Study on the cavitation characteristics and erosion mechanism of self-priming pulsed jets - Yanwei Liu; Yarui Li; Lejin Cheng; Weiqin Zuo; Haojie Jia; Chunlei Hua; Hongkai Han; Fengjie Zhang; Xiangyang Ma; Xianzhe Chen; Yu Zhang (Ocean Engineering, 2026)

Lead fraction transformation drives microbial functional recovery and coupled nutrient cycling-metal resistance networks in Pb-Zn tailings - Zhen Li; Ruoni Xie; Weihao Zhang; Jiayi Cheng; Pu Jia; Chengshuai Liu; Xuetao Guo; Li Zhuang; Tao Chen (Journal of Hazardous Materials, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Nationwide dynamic monitoring and hazardous emission quantification of crop residue burning in China: A Fengyun satellite-integrated active-fire fusion approach - Jia Li; Ying Zhou; Jianlei Lang; Xiaoyang Zhang; Chao Liu; Dongsheng Chen; Xiangchen Xia; Xingduo Li; Jing Liu; Jing Cao; Wanting Zhang; Shuiyuan Cheng (Journal of Hazardous Materials, 2026)

Speleothem multi-proxy inferred hydroclimate variability during the 2.8 ka event and its influence on human activities in southeastern China - Xiaomei Zhang; Haiwei Zhang; Ashish Sinha; Miaomiao Wang; Jian Wang; Yueer Li; Liangkang Pan; Rui Zhang; Youfeng Ning; Xuexue Jia; Baoyun Zong; Hai Cheng (Global and Planetary Change, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Tin isotope fractionation in arc magmas controlled by degassing and slab input - Wei-Cheng Jiang; Jia-Xin She; Alexandra Davidson; Chun-Fei Chen; Chris Firth; Simon Turner; Wei-Qiang Li; Trevor Ireland; Paolo A. Sossi; Jing-Hua Wu; Shane Cronin (Geochimica et Cosmochimica Acta, 2026)

The Occurrence of Emerging Per- and Polyfluoroalkyl substances (PFAS) in Indoor Dust from Different Microenvironments in South China - Yuge Liang; Xiaoyuan Guo; Chenglin Liu; Jia Zhao; Yao Cheng; Shusheng Luo; Jie Jiang; Zhong Lv; Min Hu; Tong Li; Siqi Ai; Wenhui Qiu; et al. (Environmental Pollution, 2026)

Quantifying the environmental and health benefits of ship emission control policies in Guangdong of China - Zhiruo Cheng; Yun Zhu; Zhaoxin Dong; Ji-cheng Jang; Zhiqiang You; Jia Xing; Bin Zhao; Jiabin Li; Ziyi Liu; Wang Chang (Environmental Pollution, 2026)

Laser pretreatment surface modification enhances jet electrodeposition forming performance - Zhouwei He; Xiaoyan Sun; Haikuan Chen; Xianda Jia; Shiwei Li; Shi Cheng; Youwang Hu; Pingmei Ming (Chemical Engineering Journal, 2026)

Seed priming with boron nanoparticles establishes Trans-Developmental defense to Restrict Cd translocation via cell wall remodeling in Ipomoea aquatica Forsk - Zhien Pu; Xin Qi; Jianyu Xie; Changlian Xu; Guiyin Wang; Shirong Zhang; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Bioresource Technology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

A new flavonol glycoside isolated from the stems and leaves of Astragalus membranaceus - Jia-Xin Zhao; Yun Zang; Pei Li; Jia-Ning Zhang; Si-Qi Yang; Hui-Feng Li; Yan Wang; Jin-Yan Tan; Ying-Li Wang; Yan-Gang Cheng (Natural Product Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Temperature-disease network reveals global health risks of climate change - Weican Zhang; John S. Ji; Cunrui Huang; Cheng Qian; Binghao Jia; Haidong Kan; Tiantian Li; Weiqi Zhou; Yuhai Bi; Qian Liu; Guibin Jiang (Science Bulletin, 2026)

Unveiling ecological risks of deep-sea mining: a focus on collector plumes - Xiaolei Liu; Zhihao Li; Ying Lai; Yihan Liu; Cheng Zhang; Thorsten Stoesser; Dongfang Liang; Eckart Meiburg; Rita Leal Sousa; Yonggang Jia; Yunmin Chen; Xingsen Guo (Science Bulletin, 2026)

Elevated suspended particulate matter reorganises carbon fraction in mangrove ecosystems - De Cheng; Dan Li; Shengfa Yang; Xu Zhang; Qin Zhang; Jia Li; Jie Liu; Yufeng Mao; Yi Xiao (Marine Environmental Research, 2026)

Beauvericin modulates immune responses in the silkworm, Bombyx mori: insights from cellular and transcriptomic analyses - Jinhua Fan; Yong Bi; Jia Li; Hui Su; Aiying Cheng; Baozhen Li (Journal of Invertebrate Pathology, 2026)

Convergent shifts in microbial communities: Petroleum hydrocarbon contamination suppresses matrix heterogeneity - Wenjuan Jia; Jingcheng Li; Kai Wang; Lirong Cheng; Naifu Jin; Qing Yang; Dan Zhang; Xuefeng Xia; Nuchao Xu; Mingming Wang; Jin Meng; Yi Zhu; et al. (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Construction of a carbon-conserving pathway for D-allulose production by regulating the co-utilization of acetate and glucose in engineered Escherichia coli - Longyan Zhao; Wanting Jia; Tanxiang Huang; Lei Hu; Ning Li; Xiyao Cheng; Chen Liang; Jidong Liu (Food Bioscience, 2026)

A multi-functional passive fixation lead for diagnosis and treatment of cardiac diseases - Xuandi Deng; Yiran Hu; Puqing Yao; Chunhong Yu; Juwei Yang; Ruizeng Luo; Sijing Cheng; Hao Huang; Peng Cheng; Lei Jia; Xingyao Lv; Menghan Li; et al. (Chemical Engineering Journal, 2026)

Designing virtual environments for psychological health: nature connectedness mediates the benefits of indoor virtual green exercise on restoration - Xing-xing Jia; Jing-cheng Xu; Yu-cheng Xu; Hong-yi Li; Bing Zhao; Wei Wei (Building and Environment, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Microglial Alkbh5 Deficiency Alleviates Chronic Restraint Stress-Induced Depression-like Behaviors in Mice - Ao Li; Lu Han; Jia Guo; Na Zhang; Ranxu Liu; Jingdan Zhang; Xiaoheng Li; Zengqiang Yuan; Jinbo Cheng (Neuroscience Bulletin, 2026)

Total synthesis of the proposed menominin A and its stereoisomers: identification of a highly potent isomer (1a) against RM-1 prostate cancer cells - Yu Jiang; Xin Li; Jiayi Li; Yuhan Xiao; Huiling Xu; Junqiu Zhang; Min-Jing Cheng; Junyang Liu; Jia-Lei Yan (Molecular Diversity, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Csp-π-d conjugation engineering strategy for optimizing *OH intermediate regulation of reinforced oxygen reduction reaction - Yang Lu; Yimin Mou; Ziyang Jia; Yiyi Fan; Lei Cheng; Yawen Tang; Yafei Li; Yu Wang; Hanjun Sun (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Hexavalent chromium inhibits testosterone synthesis in bovine testicular leydig cells through mitochondrial damage via BNIP3 - Hongxia Li; Jia Liu; Liwei Huang; Yu Cheng; Guoqing Zhao; Xiaolong Pan; Lijuan Huang; Pengkang Song; Le Zhao; Xuanqi Yu; Juan Xiong; Qing Tian; et al. (Reproductive Biology, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

A coupled engineering-economic model for operational planning of the Arctic Northeast Passage as a cost-effective Suez Canal alternative - Jia Huang; Qiuyan Li; Xun Gong; Lei Chen; Yuanfeng Ren; Jiao Wang; Junlin Cheng (Ocean Engineering, 2026)

Enhanced hydrolysis-acidification of BTEX-containing cabin-washing wastewater in a continuously operated reactor via iron-carbon composites and flow optimization - Jia-Hui Chen; Yu-Zhu Huang; Tsung-Lin Tsai; Xin-Hua Xu; Li-Hua Cheng (Journal of Environmental Chemical Engineering, 2026)

Contributions of SARA fractions to asphalt fume composition via experiment and ReaxFF-molecule dynamics - Ming Jia; Hui Li; Xue Zhang; Yu Cheng; Ivan Miguel De Cachinho Cordeiro; A.C.Y. Yuen; Wei Wang; Cheng Wang; Guan Heng Yeoh (Fuel, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Sourness signature during Prunus mume fruit development: Integrative insight from metabolomics, organic acid profiles, E-tongue, and computational binding simulation - Shun Gao; Yun-yi Hu; Wen-zhang Qian; Yi-xiao Xiao; Jia-li Liao; Ji-cheng Chen (Food Chemistry, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

System architecture, accuracy evaluation, and service applications of the high-precision UT1 products developed by the National Time Service Center - Xishun Li; Xuhai Yang; Yuanwei Wu; Xuan Cheng; Baoqi Sun; Dang Yao; Jia Liu; Zhe Zhang; Shougang Zhang (Science China Earth Sciences, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Correction: Associations Between Dietary Selenium Intake and Risk of Incident Arthritis: Based on UK Biobank WebQ Assessment (2009–2012) - Xuena Yang; Chen Liu; Jin Feng; Shiqiang Cheng; Chuyu Pan; Wenming Wei; Dan He; Boyue Zhao; Jingni Hui; Li Liu; Yan Wen; Yumeng Jia; et al. (Biological Trace Element Research, 2026)

Marine oil film detection method based on growing hierarchical neural gas network and multi-scale threshold segmentation - Baozhu Jia; Zekun Guo; Jin Xu; Bo Li; Yuanyuan Huang; Min Cheng; Bo Xu; Boxi Yao; Peng Liu (Marine Pollution Bulletin, 2026)

Intelligent Arctic shipping route planning with dual objectives of economy and carbon emission reduction using deep reinforcement learning - Qiuyan Li; Wenming Wu; Jia Huang; Lei Chen; Yuanfeng Ren; Xun Gong; Jiao Wang; Junlin Cheng (Ocean Engineering, 2026)

Efficient remediation of multi-PTE contaminated farmland by synergistic dissolution of soil metal oxides using wood vinegar and FeSO4 co-washing - Tianying LÜ; Xinlei JI; Xiaoxun XU; Guochun LÜ; Changlian XU; Guiyin WANG; Shirong ZHANG; Zhanbiao YANG; Zhang CHENG; Junzhuo CAI; Heng LÜ; Ting LI; et al. (Pedosphere, 2026)

Integrative morphological and genomic analyses reveal diversity, reticulate evolution, and adaptation in diploid and tetraploid Rosa species from Xinjiang - Zhongyu Tang; Zhenlong Liang; Hengning Deng; Liangying Li; Jian Ru; Shiqi Li; Jia Miao; Cheng Zhang; Xinfen Gao (Molecular Phylogenetics and Evolution, 2026)

Solid waste dumping differentially impacts soil prokaryotic, fungal, and viral communities: Insights from metagenomics - Rongzhou Jin; Can Chen; Jingru Zhang; Yanying Li; Ye Wu; Feifan Wang; Zhipeng Chen; Ting Huang; Qijie Cheng; Xinlin Yu; Pu Jia (Journal of Environmental Sciences, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Exploration of chicken lung antioxidant peptides modified by plastein reaction: Purification, identification and molecular docking - Jingwen Jia; Siyu Cheng; Lisheng Li; Tian Chen; Na Xu; Xiaomei Sun; Yun Bai; Xinglian Xu; Minyi Han (Food Bioscience, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Detoxification of T-2 toxin in human chondrocytes due to its hydroxylation by carboxylesterases and arylacetamide deacetylase in the liver - Shiqiang Cheng; Sirong Shi; Bolun Cheng; Chen Liu; Xuena Yang; Li Liu; Huan Liu; Yan Wen; Alexey A. Tinkov; Anatoly V. Skalny; Yumeng Jia; Feng Zhang (Food and Chemical Toxicology, 2026)

Towards negative-carbon biohydrogen: A dual-function wollastonite strategy for enhanced fermentation and CO2 sequestration - Weiming Li; Can Jin; Huida Duan; Fangcao Li; Zhangxun Huang; Haodong Zhao; Xiaoman Yu; Yimei Xi; Xiangfeng Zeng; Yongfeng Jia; Chi Cheng (Chemical Engineering Journal, 2026)

Platinum quantum dots-multiwalled carbon nanotubes/nickel foam composite cathode with efficient electron transport channels: Low-energy consumption degradation of tigecycline based on the SMSI effect - Jia Li; Jian Zhang; Xiaoqiang Fu; Haina Bai; Xin Cheng; Ruoyi Li (Chemical Engineering Journal, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Associations between Dietary Selenium Intake and Risk of Incident Arthritis: Based on UK Biobank WebQ Assessment (2009–2012) - Xuena Yang; Chen Liu; Jin Feng; Shiqiang Cheng; Chuyu Pan; Wenming Wei; Dan He; Boyue Zhao; Jingni Hui; Li Liu; Yan Wen; Yumeng Jia; et al. (Biological Trace Element Research, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Altered soil dominant N and P supply fractions mediate ANPP via plant nutrient uptake efficiency under alpine meadow degradation - Yiran Li; Xin Lu; Dagang Yuan; Shirong Zhang; Yulin Pu; Yuanjun Luo; Ting Li; Xiaoxun Xu; Yongxia Jia; Guiyin Wang; Ying Cheng (Journal of Environmental Management, 2026)

Multidimensional evidence of the positive effects of land use on plant biodiversity in the Hengduan Mountains - Yu Huang; Peng Luo; Honglin Li; Hao Yang; Wenwen Xie; Chuan Luo; Honghong Jia; Yue Cheng; Ming Ni; Zhixiang Sun; Zhouyu Luo; Jiang He (Journal of Environmental Management, 2026)

Machine learning-driven source apportionment and health risk assessment of multi-source groundwater pollution in highly permeable aquifers: A case study in Southwest China - Zehan Zhang; Xiaofang Yuan; Liangyuan Hu; Qianqian Yang; Yuying Cheng; Qian Li; Yongfeng Jia (Journal of Environmental Management, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Electric field-induced morphological transition between water film and water bridge in shale nanopores: A novel switching strategy for enhancing oil recovery and CO2 sequestration - Wentong Zhang; Zhi Li; Hai Huang; Zejiang Jia; Zhilin Cheng; Yapeng Tian; Yanwei Wang; Can Shi (Fuel, 2026)

An experimental, theoretical and kinetic modeling study of ammonia borane combustion - Mengmeng Jia; Jiaxin Xie; Frederick Nii Ofei Bruce; Fei Qin; Yiwen Hu; Chong-Wen Zhou; Henry Curran; Taufiq Yap Yun Hin; Song Cheng; Yang Li (Fuel, 2026)

Synchronous point-of-care visualization and sensitive detection of amantadine by pattern-assisted electrochromic-photoelectrochemical dual-mode sensor - Qinghua Cheng; Yang Chen; Yongqiang Li; Xuan Chen; Wenqi Yang; Lijuan Liang; Nengqin Jia (Food Chemistry, 2026)

Bioinspired water-driven ion reciprocating migration enables continuous power generation in cellulose-based ionic thermoelectrics - Zhiwei Tang; Jilun Guan; Shaoqiu Ke; Qi Gong; Yulin Jia; Qi Liu; Minqi Liu; Yalan Li; Fangchao Cheng; Yiqiang Wu (Chemical Engineering Journal, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

An overview of spatiotemporal variation, chemical characteristics, source apportionment, and potential influential factors of PM2.5 in coastal regions and at islands of East Asia - Po-Hsuan Yen; Wen-Hsi Cheng; Yu-Lun Tseng; Chung-Shin Yuan; Kuo-Cheng Lo; Nian-Jie Li; Jia-Yi Zhao (Atmospheric Research, 2026)

Bellidifolin mitigates doxorubicin-induced myocardial injury via regulating oxidative stress, inflammation, and apoptosis: a combination of network pharmacology and experiments - Ying Cao; Yutao Jia; Rongrong Chen; Cheng Dai; Hongyao Ge; Shenhan Duan; Aiying Li; Jiangli Wu (Journal of Molecular Histology, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Microseismic source localization method based on ABC-CS improved fusion algorithm - Wenfeng Tu; Chao Jia; Liping Li; Shuai Cheng; Diyang Chen; Yanhuan Zhang; Zhangcheng Yan; Feng Zhang (Acta Geophysica, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Marine biomaterials for advanced food packaging: From sourcing to intelligent functional design and commercial prospects - Cheng Wang; Mengru Zhang; Tong Zhang; Haitao Du; Hongmin Xia; Renwei Guan; Fengdan Guo; Xinyi Li; Mingming Wang; Xiuwen Jia; Ping Wang (Trends in Food Science & Technology, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Fluid flow and CBM productivity-CO2 injectivity evaluations induced by injection pressure and reservoir condition: Implications for CO2-ECBM injection process and drainage degree - Zhonghui Wang; Shoujian Peng; Jiang Xu; Li Jia; Liang Cheng; Jiaxuan Chen (Process Safety and Environmental Protection, 2026)

Allelopathic metabolite accumulation and microbial dysbiosis underlying continuous cropping disorder in the Panax ginseng rhizosphere - Yang-Bin Lai; Jia-Qi Wang; Li-Ye Cheng; Yuan Zhao; Jin-Qi Wang; Jin-Hea Jeoun; Qi Yan; Chang-Bao Chen; En-Peng Wang (Physiological and Molecular Plant Pathology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Tailoring Mn d-band center and valence cycling for high-efficiency catalytic ozonation of ibuprofen in pharmaceutical wastewater treatment - Yunhan Jia; Dongyao Yue; Yizhen Cheng; Zhenbei Wang; Yatao Liu; Chen Li; Fan Li; Fei Qi; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; et al. (Journal of Hazardous Materials, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Efficient and selective capture of sulfur dioxide by graphitic phase carbon nitride equipped with BmimCl-type deep eutectic solvents - Yong-Hui Liu; Shao-He Wang; Jia-Yi Yi; Jin-bo Xu; Li-Ming Cheng; Jun Du (Environmental Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Cyflumetofen disrupts the blood-brain barrier and induces neurotoxicity in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

Visualizing application of RUBY-MAT system in maize genetic transformation and gene expression pattern detection - Tengfei Jia; Shuai Zhao; Xiangyu Zhang; Yingxue Li; Kuan Cheng; Xuehui Qian; Mingli Song; Wenjing Ge; Qian Liu; Haoyue Xu; Fashuai Li; Jinhua Hu; et al. (Plant Cell Reports, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Research on pore structure and fractal characteristics of low-medium rank coals before and after acidification with H2S aqueous solution based on NMRC - Yan Wang; Haichao Wang; Xin Li; Chao Jia; Xiaoqian Cheng; Na Zhang; Bo Wang; Peng Lai; Zhenpeng Hu; Zhengkai Liao (Fuel, 2026)

Multifunctional electrospun nanofiber films towards efficient deodorization and preservation of crayfish meat (Procambarus clarkii) via a triple-synergistic strategy - Cheng Wang; ZiHan Wang; MengHuan Liu; Ning Jiang; Jia Kan; LiFang Liu; MingZhu Li; ZeFeng Yue; Hao Yu (Food Chemistry, 2026)

Optimizing wheat yields from smallholdings: Crop density-dependent benefits of wide strip sowing under varying resource availability - Jing-Wei Fan; Peiyin Jia; Shi-Cheng Li; Chu-Yi Sun; Jairo A. Palta; Shuang-Yi Kang; Xiao-Yu Lv; Li Hou; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Hydrochemical evolution and response mechanisms in multiple aquifers affected by coal mining activities: Insights from machine learning and inverse geochemical modeling - Chang Lu; Huiyong Yin; Wenju Cheng; Fangying Dong; Weijie Zhang; Biao Li; Yankun Jia (Applied Geochemistry, 2026)

Iron-nickel alloy co-reaction accelerator-based electrochemiluminescence platform with non-linear HCR-CHA cascade amplification for ultrasensitive quantitation of paraquat - Wen-Jie Zhong; Jia-Min Qin; Zhi Luo; Yun Li; Jia-Hui Zhou; Ruo Yuan; Wen-Bin Liang; Shang-Cheng Xu; Wei-Jing Yi; Yan Li (Analytica Chimica Acta, 2026)

A Transfer-Learning-Based STL–LSTM Framework for Significant Wave Height Forecasting - Guanhui Zhao; Yuyan Cheng; Yuanhao Jia; Shuang Li; Jicang Si (Journal of Marine Science and Engineering, 2026)
Significant wave height (SWH) is a key descriptor of sea state, yet providing accurate, site-specific forecasts at low computational cost remains challenging. This study proposes a transfer-learning-based framework for SWH forecasting that combines Seasonal and Trend decomposition using Loess (STL), a stacked long short-term memory (LSTM) network, and an efficient sliding-window updating scheme. First, STL is applied to decompose the SWH time series into trend, seasonal, and remainder components; the resulting sub-series are then fed into a transfer-learning architecture in which the parameters of the stacked LSTM backbone are kept fixed, and only a fully connected output layer is updated in each window. Using multi-year observations from five National Data Buoy Center (NDBC) buoys, the proposed STL-LSTM-T model is compared with a STL-LSTM configuration that is fully retrained after each STL decomposition. For example, the transfer-learning setup reduces MAE, MSE, and RMSE by up to 11.2%, 19.2%, and 14.5% at buoy 46244, respectively, while reducing the average training time per update to about one-fifth of the baseline. Parameter analyses indicate that a two-layer LSTM backbone and moderate continuous forecast step (6–12 steps) provide a good balance between predictive accuracy, error accumulation, and computational cost, making STL-LSTM-T suitable for SWH forecasting on resource-constrained platforms.

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

Anthropogenic-derived nutrition increased microbial structure and nitrogen fixation: implication from different of Manzala and Burullus Lagoons in Nile Delta - Xin-jie Chen; Xing-pan Guo; Mao-tian Li; Said A. Shetaia; Jia-yi Li; Yan Song; Alaa Salem; Hui-kun Yao; Yü Lu; Zhang-bao Cheng (Ocean & Coastal Management, 2026)

Overlooked heavy metal-induced natural organic matter property transformation and its positively resultant interaction with membrane surface - Xiaobin Ma; Zhenzhou Li; Yufei Cheng; Jinjin Jia; Jiaxuan Yang; Longfeng Hu; Hesong Wang; Meng Zhang; Xiaobin Tang; Weijia Gong; Heng Liang (Water Research, 2026)

Ilex subg. Prinos (Aquifoliaceae) from the upper Miocene of Beihai, low-latitude China: New insights for phylogeny - Bingshan Niu; Qijia Li; Hui Jia; Jianhua Jin; Cheng Quan (Review of Palaeobotany and Palynology, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Phycosphere bacterial communities mediate arsenic accumulation and speciation in coastal macroalgae: Evidence from field investigation - Cheng Li; Hanyu Sun; Yimei Xi; Yongbin Li; Xinjie Wang; Zhangxun Huang; WeiMing Li; Xiangfeng Zeng; Yongfeng Jia (Journal of Hazardous Materials, 2026)

Multi-laser hyperspectral imaging system for food quality assessment - Jia-Cheng Li; Jia-Yong Song; Ze-Sheng Qin Li-Feng Bian; Chen Yang (Innovative Food Science & Emerging Technologies, 2026)

Associations of urinary environmental phenols with obesity and lipid metabolism in children and adolescents: The expanded Chinese National Human Biomonitoring (CNHBM) project - Nan Jiang; Qi Chen; Beijing Cheng; Ke Meng; Jia Wang; Tianlin Li; Han Chen; Yinghao Liao; Hong Sun; Ran Liu (Environmental Research, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

The synergistic effect of coalbed methane recovery enhancement and CO2 sequestration in the stepwise pressure increase CO2-ECBM process: A fluid-reservoir multi-parameter dynamic evolution study - Jiaxuan Chen; Shoujian Peng; Zhonghui Wang; Jiang Xu; Li Jia; Liang Cheng; Shiyu Jiang (Chemical Engineering Journal, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Green and efficient alkaline DES pretreatment for full-component fractionation of reed biomass: Hemicelluloses, uncondensed lignin and easily digestible cellulose - Haozhi Zhang; Qian Sun; Yi-Bing Liu; Cheng-Ye Ma; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Harnessing methane for improved nitrogen removal in membrane aerated biofilm reactors: towards sustainable wastewater practices - Reham Eltawab; Ke Li; Abdallah Abdelfattah; Tamer Elsamahy; Hui Jia; Liang Cheng (Bioresource Technology, 2026)

Inversion of hourly NOx emissions through air quality monitoring data and deep learning response surface modeling - Ziyi Liu; Yun Zhu; Ji-cheng Jang; Zhaoxin Dong; Jia Xing; Bin Zhao; Jinying Li; Qipeng Wen; Dian Ding; Yujie Qin (Atmospheric Environment, 2026)

MiR-144 Regulates Cognitive Dysfunction via NLRP3 Inflammasome and FoxO1/AdipoR Pathway in T2DM Mice - Jinying Zhao; Yuliang Zhou; Shi Cheng; Jia Shen; Yahong Li; Zhipeng Xu (Molecular Neurobiology, 2026)

Microbial drivers of N₂O mitigation in soils: Role of nosZ II subclades under conservation tillage and stover mulching - Da-Cheng Hao; Yaoxuan Wang; Yuanyuan Luan; Fangbo Deng; Hongtu Xie; Yongxin Lin; Xuanqi Li; Zhongjun Jia; Lianfeng Wang (Applied Soil Ecology, 2026)

Dual-promoter systems drive plasmid loss via non-translational burden in geraniol-producing E. coli - Jia Zhou; Mengqi Cheng; Shengyang Su; Ziyi Li; Mengxin Lv; Die Hu; Xiaodie Zhang; Yilong Zhou; Hao Shi; Zhongbiao Tan; Ya Xin; Dianlong Wang; et al. (Archives of Microbiology, 2026)

Fungi and mycotoxin types, toxicity, mechanisms, and control of mycotoxin contamination: a review - Zezhi Zhang; Xiaoyan Qi; Yulin Wang; Yongli Li; Li Cheng; Qinhan Yang; Xin Yan; Xiaofang Li; Jia Luo (Food Additives & Contaminants: Part A, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Real-time tunnel risk forecasting based on rock drill signals during construction - Xingang Zhang; Liping Li; Shuai Cheng; Jiquan Zi; Yanhao Chen; Chao Jia; Qinliang Sun (Tunnelling and Underground Space Technology, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A new bisbenzoquinone with cytotoxicity from Chaetomium trilaterale - Xin-Xin Liang; Lei Li; Jia-Yi Zhang; Xin-Yue Zhang; Yi-Kun Feng; Chen Gu; Si-Cheng Jin; Xiang-Guo Meng (Phytochemistry Letters, 2025)

Calophyllum (Calophyllaceae) with high leaf mass per area from the upper Miocene of Beihai, low-latitude China - Shu-Ran Tang; Qi-Jia Li; Hui Jia; Jian-Hua Jin; Cheng Quan (Palaeoworld, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Large variations in zircon hafnium isotopes due to preferential dissolution of high-U zircon: A case study of the Lincang Batholith in SW China - Jia-Hao Fan; Jin-Cheng Xie; Li Liu; Qing Wang; Di-Cheng Zhu (Lithos, 2025)

Machine learning-driven advances in water treatment - Zhen Qiu; Zechao Zhuang; Xue Jia; Hao Li; Cheng Chen; Jinchao Shen; Bing Yu (Journal of Environmental Chemical Engineering, 2025)

Enhanced formation of nitrogenous disinfection byproducts from sulfamethoxazole during UV/chlorine treatment: Pathways, toxicity, and mitigation strategies - Xuhua Cheng; Min Zhang; Chaomin Jia; Manhong Miao; Xiaoyu Tang; Shasha Zhao; Yao Li (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Construction of a machine learning-based prediction model for rice varieties—cooking—mastication - Mengjie Ma; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Mingyi Shen; Jinyi Wu; Jia Liu; Yan Hong (Food Research International, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Prebiotic effects and functional insights into gut microbiota mediated by Qingke β-glucan of different molecular weights in vitro fermentation - Lan Zhao; Xinran Yang; Peijie Ye; Zhihai Lan; Jiale Cheng; Li Li; Jia Wu; Wei Xu; Huibin Chen (Bioactive Carbohydrates and Dietary Fibre, 2025)

Alteration of Cecal Microbiota by Antimicrobial Peptides Enhances the Rational and Efficient Utilization of Nutrients in Holstein Bulls - Jinping Shi; Yu Lei; Zemin Li; Li Jia; Pengjia He; Qiang Cheng; Zhao Zhang; Zhaomin Lei (Probiotics and Antimicrobial Proteins, 2025)

Role of mitochondrial metabolism in ischemic stroke and natural products intervention - Xuan-Hao Zhang; Ying Li; Cheng-Yu Jin; Jia-Le Zhang; Yang-Peng Yan; Jia-Xiu Guo; Xin Lu; Han-Qing Pang; Yong-Juan Zhao (Molecular Biology Reports, 2025)

Enhanced identification of novel pathogenic variants in hereditary hearing loss through physical phasing with integrated short and long-read sequencing data - Lu Kang; Qian Zhang; Chao Wang; Jia Geng; Xinlei Li; Mingjun Zhong; Sihan Liu; Xuegang Wang; Yu Lu; Jing Cheng; Yongxin Ma; Fengxiao Bu; et al. (Molecular Genetics and Genomics, 2025)

Complete mitochondrial genome sequence of Nannostomus eques and comparative analysis with Nannostomus beckfordi - Xian-Ru Li; Cheng-He Sun; Yi-Jing Zhan; Shuang-Xi Jia; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Novel multi-component synergistic bioink that balances biocompatibility and mechanical strength for cartilage regeneration - Zijun Ma; Wendan Jia; Xiaoyuan Wang; Rong Cheng; Lu Han; Meng Li; Xiaoning Yang; Shengbo Sang (Journal of Zhejiang University-SCIENCE B, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Genesis of the Heima zinnwaldite deposit in the Gongshan region, Southeast Tibetan plateau - Shiping Li; Zechuan Wang; Jing Wang; Zhen Jia; Jialong Cheng; Fuchuan Chen; Shiyin Xiao; Chaofang Dong; Yitian Luo (Acta Geochimica, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

A new dammarane-type triterpenoid saponin from the leaves of sour jujube - Jin-Yan Tan; Pei Li; Si-Qi Yang; Jia-Ning Zhang; Yan-Gang Cheng (Natural Product Research, 2025)

Chrysin enhances sunitinib sensitivity in renal cell carcinoma by inducing ferroptosis via targeting PI3K/Akt/GPX4 pathway - Zixuan Chen; Weiyuan Li; Boshen Jia; Guohuan Yin; Zongrun Sun; Yanjun Tong; Sheng Cheng; Min Liu (Toxicology and Applied Pharmacology, 2025)

Study on hydrogen storage properties of Ca atom modified γ-graphyne - Jun-wei Liu; Jia-cheng Li; Cai-he Fan; Ling Ou; Ying-zhe Zhang (Process Safety and Environmental Protection, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Interpreting CO2 monitoring for assessing airborne transmission risk in indoor environments - Wei Jia; Pan Cheng; Luca Fontana; Pak Wai Chan; Pawel Wargocki; Yuguo Li (Journal of Hazardous Materials, 2025)

Occurrence and fugacity model simulation of organophosphate esters in atmosphere-soil-vegetation, Fildes peninsula, Antarctica - Guanjie Cheng; Ruijing Li; Yunfeng Xu; Chao Hou; Xuan Jia; Bing Li; Hui Gao; Shuaichen Jin; Liang Kong; Guangshui Na (Journal of Environmental Sciences, 2025)

Closing in on carbonate uranium isotopes as a paleo-redox proxy based on continuous records from Late Oligocene to Holocene island carbonates - Guolin Xiong; Feifei Zhang; Yi-Bo Lin; Guang-Yi Wei; Na Li; Mengchun Cao; Xuexue Jia; Jian Wang; Wen Yan; Hai Cheng; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Network-based investigation of norfloxacin-induced nasal immune-related inflammatory responses in carp (Cyprinus carpio) and its cross-species implications for olfactory immune disturbance - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Zhi-Hua Li (Fish & Shellfish Immunology, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

Design of EVOH nanofibers aerogel integrated with phase change materials for sustained solar-driven seawater desalination - Ye Zhang; Yi Wu; Shanshan Li; Mengqi Wang; Ke Liu; Ming Xia; Qin Cheng; Jia Xu; Shanshan He; Dong Wang (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Interactions of sesamol with starches of different amylose to amylopectin ratios during co-gelatinization condition - Xiaoqiang Li; Hongyue Zhao; Ruobing Jia; Jia Cao; Yaxing Xie; Zeyu Peng; Jianjun Cheng (Carbohydrate Polymers, 2025)

Lipidomic profiling of cutaneous surface lipid alterations in sensitive scalp in Beijing - Ran Li; Qian Jiao; Liya Song; Youjie He; Huaming He; Cheng Zhou; Yan Jia (Chemistry and Physics of Lipids, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Impact of pretreatment methods on hydrogen and ethanol co-production from brown algae: Energy recovery and cost analysis - Zhongliang Shi; Chi Cheng; Mengyang Bian; Weiming Li; Yimei Xi; Shuhua Yao; Xiangfeng Zeng; Yongfeng Jia (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Hydrophobic surface modification of Zr-based metal–organic frameworks with silane for oxidative desulfurization - Gexian Li; Linyu You; Jilong Cheng; Zekai Liu; Jinbiao Wu; Linfeng Zhang; Huadong Wu; Jia Guo (Fuel, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Seismic performance prediction and interpretation of RC bridges under vehicle-bridge interaction: From VBI system simulation to ensemble learning surrogate models - Liang Luo; Yan Li; Hanfang Dai; Hang Sun; Mingming Jia; Huan Yuan; Xuanhao Cheng (Engineering Structures, 2025)

Real-time geological hazard detection ahead of tunnel face using blast-induced seismic signals: A case study in Tashan Tunnel, China - Xingang Zhang; Shuai Cheng; Jiquan Zi; Liping Li; Qinliang Sun; Chao Jia; Hao Wang (Engineering Geology, 2025)

Ultrarobust eutectogels with nanophase separation structure for self-damping pressure sensing - Zong-Ju Chen; Yu-Qiong Sun; Zi-Han Zhao; Li-Jia Pan; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Efficient Hg(II) removal using recyclable poly(thioctic acid)/SH-UiO-66 functionalized polyacrylonitrile fiber: Multifunctional binding strategy - Ningge Jian; Gaoran Zhang; Hongli Liu; Di Wu; Jia Wang; Yuxin Wang; Yi Cheng; Qingyuan Liu; Yongjun Wu; Li-e Liu (Chemical Engineering Journal, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Advances in Tetrabromobisphenol A (TBBPA) degradation: A comprehensive review of physicochemical and biotechnological strategies - Wei-Lei Jin; Gui-Xuan Dong; Yang Liu; Yu-Chen Sun; Jia-Cheng Li; Yan Li; Juan Xu (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Vertically oriented roots affect soil water infiltration by decomposition and altering soil structure: An examination based on CT technology and innovation in soil infiltration research methods - Yingzhou Tang; Jingwei Lian; Chong Li; Xuefei Cheng; Zhaohui Jia; Xin Liu; G. Geoff Wang; Lu Zhai; Lei Wang; Dezong Sui; Jinchi Zhang (Plant and Soil, 2025)

HFIP-driven Schmidt-type reaction enables chromone-3-carbonitriles and its applications - Jia Xu; Jie Lei; Li-Xin Zhang; Shan Yu; Cheng-He Zhou; Zhi-Gang Xu; Hong-Wei Du; Zhong-Zhu Chen (Molecular Diversity, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Challenges in Predicting Yangtze River Basin Summer Temperatures: The Role of Atmospheric Circulation and Tropical SST Forcing - Jinqing Zuo; Xiaolong Jia; Tao Feng; Shanjun Cheng; Hui Gao; Xuannan Wang; Li Li; Jingpeng Liu; Jie Tang; Lei Wang (International Journal of Climatology, 2025)
The densely populated and economically crucial Yangtze River Basin (YRB) in China has experienced an increasing trend of high‐temperature events during recent summers, highlighting the importance of skillful seasonal prediction for effective mitigation and adaptation. However, the sources of predictability and origins of prediction errors for YRB summer temperatures remain poorly understood. This study investigates the predictability of YRB summer (July–August) temperatures using hindcasts from three state‐of‐the‐art dynamical climate models to better understand these sources. While all models demonstrate some skill at a 0‐month lead, this capability becomes severely limited at lead times of 1 month or longer. Analysis of the models' ability to simulate the driving physical mechanisms reveals that while they reasonably capture the observed relationship between YRB summer temperatures and the associated local atmospheric circulation pattern linked to a Eurasian mid‐to‐high latitude wave train, significant uncertainties in predicting this wave train itself constrain overall skill. Furthermore, observational evidence shows a significant out‐of‐phase relationship between YRB summer temperatures and concurrent sea surface temperature (SST) anomalies in the equatorial central–eastern Pacific, a relationship that the models fail to reproduce. This failure stems from varying model biases in simulating the atmospheric circulation response to equatorial Pacific SST forcing, hindering their ability to capture the Pacific–YRB teleconnection. Therefore, deficiencies in simulating both the Eurasian circulation and the tropical Pacific forcing significantly contribute to the limited seasonal prediction skill for YRB summer temperatures, underscoring the need for improved representation of mid‐latitude dynamics, tropical air–sea interactions and associated atmospheric teleconnections in dynamical models.

Molecular docking-based design of novel tricyclic tetrahydropyridothienopyrimidinone derivatives as AChE/MAO-B dual inhibitors - Juan Zhang; Yue Li; Jia-Dong Shao; Guo Wei; Nai-Yu Zhang; Kong-Kai Zhu; Kai-Ming Wang; Cheng-Shi Jiang; Jia-Hong Wang (Molecular Diversity, 2025)

Effects of calcium levels in water on growth, calcium deposition, molting, and immunity of Chinese mitten crab (Eriocheir sinensis) - Ronghua Zhou; Qiyong Qiu; Yingying Zhou; Shiyu Qin; Xiaoyan Jia; Wei Qiang; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Edge-electron induced ferrimagnetic effect to accelerate interfacial desolvation kinetics toward dendrite-free Zn metal batteries - Haifeng Yang; Fangqi Liu; Bixian Chen; Xiaomin Cheng; Qinghua Guan; Jing Dong; Teng Li; Lujie Jia; Wenbin Wang; Jing Zhang; Jiqiang Jia; Yongzheng Zhang; et al. (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Quantification of the Thermal Contact Resistance at the Bentonite–Granite Interface in the Barrier System of High-level Nuclear Waste Disposal Repositories - Zheng-Wei Li; Yi-Xuan Cheng; Chuan-Yuan Huang; Xin-Xin Chen; Jia-Cheng Miao; Tao Han (Rock Mechanics and Rock Engineering, 2025)

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Global, regional and national burden of lung cancer attributable to PM2.5 air pollution: Trends from 1990 to 2021 with projections to 2045 - Yingfan Deng; Zengbin Li; Pan Zhang; Yang Yang; Yuhan Xie; Yutong Cheng; Shuiyan Yu; Guixian Zhu; Lili Han; Lijun Jia; Wentao Xi; Pei Wang; et al. (Journal of Environmental Management, 2025)

Mineralogical and chronological records of strong shock metamorphism in pigeonite cumulate eucrite Northwest Africa 8326 - Lang Zhang; Ai-Cheng Zhang; Xiao-Wen Liu; Yan-Jun Guo; Jia-Ni Chen; Yuan-Yun Wen; Qiu-Li Li; Yu Liu; Xiao-Xiao Ling; Jin S. Zhang (Geochimica et Cosmochimica Acta, 2025)

MOF-based high-entropy-alloy evaporator featuring enhanced interband transitions for efficient solar steam and green electricity generation - Chenyang Dai; Jia-Han Zhang; Cheng-Yu He; Rongrong Dai; Likun Pan; Yusuke Yamauchi; Jing Zhang; Zhengtong Li; Xingtao Xu (Chemical Engineering Journal, 2025)

Characterization and Risk Assessment of Heavy Metals in Topsoil of Agricultural Land from an Agate Dyeing Village - Haodong Wang; Ye Li; Jia Fu; Shanshan Feng; Quanguo Cheng; Jianbing Wei (Water, Air, & Soil Pollution, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Analysis and Control Techniques of Ultra-Shallow Buried Tunnels in Rain-Affected Backfill Soil - Peng-cheng Wang; Li-yang Su; Shu-jie Shang; Xiang-yu Jia; Wei-teng Li; Feng-chuan Jiang; Chun-qing Liu; Xin-jie Man (Geotechnical and Geological Engineering, 2025)

Seismic ahead-prospecting method based on delayed blasting excitation in the tunnel face: A case study - Chao Jia; Shuai Cheng; Liping Li; Yanhao Chen (Tunnelling and Underground Space Technology, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Melatonin improves aluminum tolerance in soybean through modification of cell wall and vacuolar compartmentalization of aluminum - Huanan Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Junjun Huang; Huahua Wang (Journal of Plant Physiology, 2025)

Experimental evaluation of the effectiveness of stable isotopic ratios to characterize soil and groundwater evaporation in watersheds - Yundi Hu; Lu Zhao; Zhongfa Zhou; Min Zhao; Qiuwen Zhou; Cheng Zeng; Yuchao Zhang; Zhengzhou Huang; Dengchao Wang; Yueqing Zhang; Hongdai Fan; Hang Li; et al. (Journal of Hydrology, 2025)

HvAIR12 confers aluminum tolerance in barley by H2O2-mediated activation of HvEXPA4 to facilitate aluminum detoxification and improve root growth - Cheng-Wei Qiu; Min Shi; Quncuo Zhaxi; Xue Feng; Yong Jia; Chengdao Li; Feibo Wu (Journal of Hazardous Materials, 2025)

Removal of copper, lead and cadmium from water through enzyme-induced carbonate precipitation by soybean urease - Haipeng Zeng; Bingbing Jin; Shiming Xu; Li Han; Jiaqian Wang; Hui Jia; Malcom Frimpong Dapaah; Liang Cheng (Environmental Research, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Terracing stabilizes and enhances soil organic carbon sequestration benefits of revegetation on the Loess Plateau, China - Hui Cheng; Hao Feng; Xiaoping Zhang; Zhiguang Li; Kaiyang Yu; Hongbin Ma; Jia Xu (CATENA, 2025)

Analysis of fractal and energy characteristics of low-temperature concrete under an impact load - Hongming Su; Zhiwu Zhu; Wurong Jia; Tao Li; Zhengqiang Cheng; Hongyu Xiang (Cold Regions Science and Technology, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Dimorphic floral characteristics and heteromorphic self-incompatibility of Primula forbesii - Ying Liu; Wanpei Lu; Xiaoyuan Li; Weiru Yang; Tangren Cheng; Jia Wang; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Endothelial GTPBP3 directs developmental angiogenesis and neovascularization after limb ischemia via the mtROS/HRl/ATF4/mTORC1 axis - Donglu Qin; Jiarui Hu; Yang Yang; Xin Li; Jia He; Jin Chen; Xin Guo; Cheng Wei; Fengjiao Wang; Ting Yi; Chenyu Li; Bilian Yu (Angiogenesis, 2025)

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Low-dose tire wear chemical 6PPD-Q exposure elicit fatty liver via promoting fatty acid biosynthesis in ICR mice - Lili Wang; Weitian Tang; Nan Sun; Jia Lv; Jiayue Hu; Lin Tao; Cheng Zhang; Hua Wang; Li Chen; De-Xiang Xu; Yihao Zhang; Yichao Huang (Journal of Hazardous Materials, 2025)

Reconstruction of surface defects in Bi2MoO6 induced by amorphous ZnO for ultra-fast photocatalytic purification of Cr(VI) - Li-li Yao; Cheng-zhao Jin; Xin-an Yang; Wang-jia Xia; Wang-bing Zhang (Journal of Environmental Chemical Engineering, 2025)

Porphyrinic based hydrogen-bonded organic framework/TiO2 nanocomposites for efficient photocatalytic degradation of sulfadiazine - Chunying Li; Yu Zhang; Mengfei Tian; Naveed Ahmad; Kaitao Jia; Zidan Luo; Bin Qiao; Jiabo Cheng; Chunjian Zhao (Journal of Environmental Sciences, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Epigallocatechin gallate (EGCG) slows fructooligosaccharides fermentation via inulinase suppression and promotes beneficial gut bacteria in vitro - Bo Cheng; Hongyan Feng; Tingting Chen; Fei Jia; Cheng Li; Xiaowei Zhang (Food Bioscience, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

The mutual effect of dietary fiber and polyphenol on gut microbiota: Implications for the metabolic and microbial modulation and associated health benefits - Bo Cheng; Hongyan Feng; Cheng Li; Fei Jia; Xiaowei Zhang (Carbohydrate Polymers, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Rapid classification and identification of chemical compositions of Pu-zhi-hui-ling decoction by UHPLC-Q-Orbitrap HRMS - Jia Shao; Yanxue Zheng; Yuanyuan Wang; Guohui Li; Jinxia Wei; Wenbo Cheng; Yubo Li (Natural Product Research, 2025)

Toxic effects of emerging pollutants on mucosal organs of teleost fish: A review focusing on mucosal microbiota, physical barrier and immune barrier - Jia-Ming Zhang; Ping Li; Cheng-Zhuang Chen; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Hydroclimate variability in southwest China during Marine Isotope Stage 9: Insights from multi–proxy stalagmite records - Wei Jia; Yan Yang; Hai Cheng; Tingyong Li; Jingyao Zhao; Shaoneng He; Guangxin Liu; Xiao Liu; Lidan Lei; Mingyang Li; R. Lawrence Edwards (Quaternary Science Reviews, 2025)

Long-term response mechanism of bacterial communities to chemical oxidation remediation in petroleum hydrocarbon contaminated groundwater - Wenjuan Jia; Zhimao Deng; Marco Petrangeli Papini; Lirong Cheng; Naifu Jin; Dan Zhang; Zhengyan Li; Dayi Zhang; Yi Zhu; Aizhong Ding (Journal of Hazardous Materials, 2025)

A half-century drying in Gobi Oasis, possible role of ENSO and warming/moistening of Northwest China - Qiang Li; Yifan Wu; Xiangyu Duan; Yu Liu; Changfeng Sun; Huiming Song; Qiufang Cai; Meng Ren; Jiachuan Wang; Zichun Jia; Hai Cheng (Global and Planetary Change, 2025)

Antiscalant-free strategy for nanofiltration: Prolonged induction period of gypsum crystallization at ultralow pressure - Longfeng Hu; Zihan Liu; Jinjin Jia; Nuo Cheng; Shu Jiang; Hesong Wang; Jiaxuan Yang; Jinlong Wang; Guibai Li; Heng Liang (Desalination, 2025)

Thoracic perfusion of Esculentoside A-loaded thermosensitive hydrogel for the treatment of malignant pleural effusion in lung cancer - Jia You; Kun Shi; Xi Yang; Huawei Li; Lingnan Zheng; Yuanfeng Wei; JingYi Xu; Yue Li; Zhiyong Qian; Cheng Yi (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Geomorphic and geologic controls on large-scale landslides in the Himalayan region of China - Yu-Feng Wang; Peng-Hai Chen; Jia-Zhen Qian; Qian-Gong Cheng; Jie Ming; Chuan-bao Li (Landslides, 2025)

An Attempt of Combining Oak and Pine Trees to Enhance Monsoonal Precipitation Reconstruction in the East Qinling Mountains - Qiang Li; Jiachuan Wang; Yalan Yan; Wenxuan Pang; Yang Xu; Yu Liu; Huiming Song; Changfeng Sun; Zichun Jia; Yifan Wu; Hai Cheng (International Journal of Climatology, 2025)
Short‐term meteorological observations often limit our understanding of regional climate change over historical periods. Dendroclimatology provides an effective means for overcoming this limitation by extending the climate record. In China, most tree‐ring studies focus on coniferous species. But this study innovatively combines both Liaodong oak and Chinese pine trees to establish a new synthesis chronology in the East Qinling Mountains. The new synthesis chronology showed a significantly high correlation with observed April–June precipitation ( r = 0.747, n = 41, p R 2 > 40%). Using this synthesis chronology, we reconstructed a 163‐year precipitation series that offers a robust spatiotemporal representation of the marginal East Asian Summer Monsoon (EASM) region through spatial correlation analysis and comparison with surrounding hydroclimate reconstructions. The several extreme drought periods (1871–1881, 1917–1931, and 1957–1973) and extreme wet periods (1888–1899, 1906–1916, and 1985–1995) were detected from the reconstruction. Additionally, it showed significant synchronisation with the EASM indices ( p

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Enhancing mine safety and mitigating greenhouse gas emissions: A comprehensive analysis of fluid migration dynamics in coalbed methane co-production - Li Jia; Liang Wang; Yuanping Cheng; Jiang Xu; Baisheng Nie; Shoujian Peng (Process Safety and Environmental Protection, 2025)

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Quantitative microbial risk assessment for on-site employees in a wastewater treatment plant and implicated surrounding residents exposed to S. aureus bioaerosols - Wei-di Wan; Jia-xin Ma; Tian-nuo Lai; Yong-tang Yan; Wajid Ali; Zhen Hu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Self-powered multisensory neuromorphic device with auditory and rotational perception integration inspired by the labyrinth of the inner ear - Feiyu Wang; Jia-Han Zhang; Shuo Ke; Jiean Li; Fengchang Huang; Wen Cheng; Yi Shi; Lijia Pan (Chemical Engineering Journal, 2025)

Network pharmacology-based strategy to reveal the mechanism of pinocembrin against ovarian cancer - Guanghui Wang; Jianxiang Cheng; Meizhen Yao; Jing Li; Ting Chen; Jia Zhang; Wensheng Du; Youguo Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Knockdown of the Clock gene in the liver aggravates MASLD in mice via inhibiting lipophagy - Shuhong Yang; Xinxin Ren; Jia Liu; Yan Lei; Minqian Li; Fang Wang; Shuting Cheng; Junjie Ying; Jie Ding; Xiaohui Chen (Molecular and Cellular Biochemistry, 2025)

Light-activated aptasensor for plug-and-play detection of Aflatoxin B1 in food samples - Yongmei Jia; Bing Han; Guohua Zhou; Zhiguo Li; Mingyue Xue; Bo Liang; Peilian Liu; Yong Cheng (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Two rare C14-C15 chemical bond-breaking 7/5/5 skeleton schinortriterpenoids and their neuroprotective activities of against CORT-induced apoptosis of PC12 from the Schisandra chinensis leaves and stems - Jian Li; Yong-Guo Li; Yong-Cheng Yang; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2025)

Sex differences in aristolochic acid I-induced nephrotoxicity in mice and the effect of estradiol - Qianru Wang; Jiuwen Hou; Fan Shui; Jia Tang; Jianjun Du; Cheng Chen; Wenjing Zhang; Maggie Shiliu Tu; Chunhui Li; Qibing Mei (Toxicology and Applied Pharmacology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Stress-induced self-assembly of hierarchically twisted stripe arrays - Zhenghao Zhang; Zekai Zhang; Junyu Hou; Yiyue Zhao; Jia Jia; Jiwei Wang; Jie Zhao; Cheng Lian; Angang Dong; Dongyuan Zhao; Wei Li (Science Bulletin, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

The coupling development of energy-economy-environment from the perspective of rural households: Insights into preventing returning to poverty - Xin Cheng; Ziyi Yu; Jingyue Gao; Li Chen; Yaru Jiang; Yanting Liu; Yan Dai; Jia Chen; Chaofan Wang; Chenfeng Wang; Yongjie Zheng; Huimin Zhou; et al. (Land Use Policy, 2025)

The role of GSK3β signaling mediated lysosomal biosynthesis dysregulation in fluoride-induced neurological impairment - Yi Cheng; Yuhui Du; Yue Hu; Xinying Wang; Qingyuan Li; Xi Yan; Ming Dou; Weihua Jia; Fangfang Yu; Yue Ba; Guoyu Zhou (Food and Chemical Toxicology, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

Efficiently selective inactivation of Gram-positive bacteria by MCM-41 molecular sieve-supported copper-based self-cascading nanozymes - Xue-Yao Pang; Fan-Xiang Meng; Cheng Ma; Si-Yang Ni; Zi-Han Jia; Bo Li; Yu-Xiang Liu; Wei-Wei Gao (Chemical Engineering Journal, 2025)

Synthesis of covalent organic frameworks with homopore and heteropore in betaine–HFIP based deep eutectic solvents: Application in intelligent colorimetric sensor - Lingling Li; Qiuyi Liu; Dandan Wang; Mingyue Wang; Yu Cai; Yuqiang Xiao; Yue Lan; Jiaqi Hu; Panpan Cheng; Jia Zeng; Zhou Li; Yidong Liu; et al. (Chemical Engineering Journal, 2025)

Recyclable and low-content deep eutectic solvent pretreatment at room temperature for fractionating uncondensed lignin and enhancing enzymatic saccharification - Cheng-Ye Ma; Qian Sun; Ling-Hua Xu; Haozhi Zhang; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2025)

China’s Yangtze River drought: A cascade of impacts from mountains to sea - Nan Jia; Jie Cheng; Yinshuai Li; Lilin Zheng; Wen Song; Ruishan Chen; Annah Zhu (Science China Earth Sciences, 2025)

Correlation of cyclosporine A blood concentration with kidney injury for pediatric patients after hematopoietic stem cell transplantation: a retrospective cohort study - Wei Shi; Xin Qiu; Liang Huang; Linan Zeng; Runxin Lu; Hailong Li; Kun Zou; Zhijun Jia; Guo Cheng; Qin Yu; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

Altered resting-state functional connectivity of amygdala subregions in adults with subthreshold depression after aerobic exercise - Yihe Wang; Mengqi Zhao; Qin Li; Zeqi Hao; Jiaxi Zhang; Lina Huang; Qingguo Ding; Zhixiang Cheng; Jianxin Zhang; Huayun Li; Xize Jia (Brain Imaging and Behavior, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Re-insight of the degradation of perfluorooctanoic acid (PFOA) through three-dimensional rotating gliding arc plasma - Di Tian; Jiushan Cheng; Mengge Jia; Ruoxi Li; Zhongwei Liu; Qiang Chen (Process Safety and Environmental Protection, 2025)

A wheat phytohormone atlas spanning major tissues across the entire life cycle provides novel insights into cytokinin and jasmonic acid interplay - Huanran Yin; Wei Liu; Xin Hu; Jingqi Jia; Mengmeng Liu; Jiaqi Wei; Yikeng Cheng; Xin Gong; Qiang Li; Wenhao Yan; Jizeng Jia; Lifeng Gao; et al. (Molecular Plant, 2025)

Heavy metals migration and in-situ solidification in the co-combustion of solid waste fuels: Rules and differences - Shuning Qin; Li Jia; Xiaolei Qiao; Chenxing Wang; Baihe Guo; Xinyue Chang; Peng Cheng; Yan Jin (Journal of Environmental Chemical Engineering, 2025)

Exploring the effect of pH-shifting on the gel properties and interaction of heat-induced Flammulina velutipes polysaccharide-porcine myofibrillar protein for improving the quality of Flammulina velutipes-pork patties - Zheming Wang; Liang Li; Fengying Jia; Jiaman Wu; Wen Jin; Wenfei Zhao; Jinling Cao; Yanfen Cheng; Lei Shi; Shaojun Yun; Cuiping Feng (Food Chemistry, 2025)

Single-cell transcriptome sequencing analysis of physiological and immune profiling of crucian carp (Carassius auratus) gills - Zhi-Guang Hou; Meng-Chao Xing; Jia-Xing Luo; Yi-Huan Xu; Li-Han Zhang; Xiao-Wei Gao; Jiang-Jiang Wang; Fazhan Hanafiah; Waiho Khor; Xin Hao; Xin Zhao; Cheng-Bin Wu (Fish & Shellfish Immunology, 2025)

Robust photothermal self-healing superhydrophobic composite coating for durable anti/de-icing applications - Jie zhu; Wen Li; Tong Wang; Huimeng Feng; Jia Cheng; Cunguo Lin; Xin Wang; Wei Wang; Shougang Chen (Chemical Engineering Journal, 2025)

Integrating multi-virion aerosols into the Wells–Riley equation with a focus on short-range exposure - Yuguo Li; Wei Jia; Pan Cheng; Ao Li; Hua Qian (Building and Environment, 2025)

Synthesis, molecular docking studies of formononetin derivatives as potent Bax agonists for anticancer activity - Wei-Dong Jia; Xue Bai; Qian-Qian Ma; Ming Bian; Chun-Mei Bai; Di Li; Li-Fei Li; Cheng-xi Wei; Li-Jun Yu (Natural Product Research, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

α-Glucosidase inhibitory activities of aromatic compounds from the rhizomes of Alpinia galanga - Yueh-Hung Cheng; Po-Chun Chen; Zakhele M. Dlamini; Jia-Wei Li; Bongani S. Dlamini; Yu-Kuo Chen; Chi-I Chang (Medicinal Chemistry Research, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

The interaction strength of keystone module in cross-kingdom network determines microbial carbon metabolic stability under temperature stress - Kaiye Chen; Hongmei Yu; Hui Wang; Peng Li; Kun Cheng; Tao Wu; Shuntao Chen; Zhenyi Jia; Xuefeng Xie; Lingyue Zhu (Applied Soil Ecology, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Changes of Yancheng coastline near 20 years based on remote sensing technology - Yu Song; Shuang Yang; Dongxu Li; Yubao Shao; Jie Cheng; Xingxing Shan; Li Cao; Silong Li; Chao Xie; Li Shan; Delong Tian; Hao Wang; et al. (Marine Georesources & Geotechnology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

SLC40A1+ macrophages contribute to the immunosuppressive tumor microenvironment in EGFR-mutated lung cancer - Xinyu Song; Zongjuan Li; Xuanhe Wang; He Du; Yijun Jia; Shen Chen; Anwen Xiong; Wei Li; Xuefei Li; Lei Cheng; Chao Zhao; Lei Wang; et al. (Science Bulletin, 2025)

First retrieval of 24-hourly 1-km-resolution gapless surface ozone (O3) from space in China using artificial intelligence: Diurnal variations and implications for air quality and phytotoxicity - Fan Cheng; Zhanqing Li; Zeyu Yang; Ruohan Li; Dongdong Wang; Aolin Jia; Ke Li; Bin Zhao; Shuxiao Wang; Dejia Yin; Shengyue Li; Wenhao Xue; et al. (Remote Sensing of Environment, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Study on the evolution of ecological flow in river and its guarantee degree during different hydrological periods - Xue Chen; Qin Li; Zhuo Jia; Rui Xiao; Zhijin Cheng; Yuhao Peng (Journal of Cleaner Production, 2025)

A forecasting tool for optimized emission control strategies to achieve short-term air quality attainment - Zhaoxin Dong; Shuxiao Wang; Yueqi Jiang; Jia Xing; Dian Ding; Fenfen Zhang; Dejia Yin; Qian Song; Jingyu An; Hongli Wang; Cheng Huang; Qian Wang; et al. (Journal of Environmental Management, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Influence of geometric parameters on ejector acoustics and efficiency in ejector refrigeration system - Wenliang Li; Qingyang Han; Cheng Wang; Hailun Zhang; Lei Jia; Lei Wang; Wenxu Sun; Haoyuan Xue (International Journal of Refrigeration, 2025)

Petrogenesis of the unbrecciated pigeonite cumulate eucrite Northwest Africa 8326: Bridging the gap between eucrites and diogenites - Xiao-Wen Liu; Ai-Cheng Zhang; Li-Hui Chen; Lang Zhang; Xiao-Jun Wang; Jia Liu; Li-Ping Qin; Yu Liu; Qiu-Li Li; Xiao-Xiao Ling (Geochimica et Cosmochimica Acta, 2025)

Preparation of resistant starch from lotus root by autoclaving and multi-enzyme hydrolysis: Structural characteristics, physicochemical properties and anti-inflammatory activities - Qingyang Cheng; Shiyao Jia; Chao Tang; Juan Kan; Chunlu Qian; Changhai Jin; Jun Liu; Liangjun Li (Food Bioscience, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

A power-law distribution of infectious quanta for the top 30% of SARS-CoV-2-infected individuals - Pan Cheng; Wei Jia; Li Liu; Hui-Ling Yen; Yuguo Li (Building and Environment, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Middle to late Miocene cooling and drying in the northern Tibetan Plateau based on evidence from plant-insect interactions - Cui Wang; Yusheng (Chris) Liu; Natalia Maslova; Hui Jia; Qijia Li; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Shortening the early diagnostic window of Hg2+-induced liver injury with a H2O2-activated fluorescence/afterglow imaging assay - Longxuan Li; Jia Li; Xin Liu; Xuan Zhao; Ao Zhang; Yun Deng; Cheng Peng; Zhixing Cao; Wim Dehaen; Yuyu Fang (Journal of Hazardous Materials, 2024)

Quantifying multi-virion aerosols in respiratory infection transmission - Pan Cheng; Wei Jia; Li Liu; Hui-Ling Yen; Yuguo Li (Journal of Hazardous Materials, 2024)

Exogenous melatonin improves peanut field productivity and quality at reduced nitrogen application - Lijie Li; Xiangguo Cheng; Yi Zhang; Dana Kohtz; Xiaohui Wang; Xiaotian Zhang; Xiangjun Kong; Huiyun Xue; Peipei Jia; Na Bai; Zengqiang Li; Peng Xiao; et al. (Field Crops Research, 2024)

Fate of antibiotic resistance genes during sludge anaerobic fermentation: Roles of different sludge pretreatment - Yali Wang; Boya Cheng; Yuanyuan Jia; Yuxuan Qi; Hang Li; Qiushuo Zhang; Hongjie Wang (Environmental Research, 2024)

Association between phthalates exposure and all-cause mortality among diabetic cases: A prospective study - Xu Cheng; Shiyang Zhang; Jun An; Chengyong Jia; Xin Zhang; Peiwen Li; Youbing Guan; Yan Yan; Zhuoya Zhao; Yuenan Liu; Tao Jing; Suli Huang; et al. (Environmental Pollution, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Polyelectrolyte intercalated two-dimensional covalent organic framework membranes for efficient desalination - Beixi Jia; Yu Zheng; Zhichao Li; Kai Xu; Hui Wang; Lijuan Cheng; Hongjian Wang; Zhuang Liu; Runnan Zhang; Zhongyi Jiang (Desalination, 2024)

Towards wearable multifunctional cellulose nanofiber/silver nanowire/graphene oxide film: Electromagnetic protection, antibacterial, and motion monitoring - Zheng Wang; Shi-Bo Li; Xiao Yang; Hao Wang; Li-Jing Xie; Ze-Chao Tao; Qing-Qiang Kong; Shou-Chun Zhang; Hui Jia; Dong Jiang; Cheng-Meng Chen (Chemical Engineering Journal, 2024)

Inversing NOx emissions based on an optimization model that combines a source-receptor relationship correction matrix and monitoring data: A case study in Linyi, China - Mengzhen Li; Jianlei Lang; Ying Zhou; Zeya Shen; Dongsheng Chen; Jia Li; Shuiyuan Cheng (Atmospheric Environment, 2024)

Two genes encoding a bacterial-type ABC transporter function in aluminum tolerance in soybean - Junjun Huang; Huanan Li; Yiwei Chen; Xiaoyu Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Huahua Wang (Plant Cell Reports, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Neuroprotective Effect of a Multistrain Probiotic Mixture in SOD1G93A Mice by Reducing SOD1 Aggregation and Targeting the Microbiota-Gut-Brain Axis - Zikai Xin; Cheng Xin; Jia Huo; Qi Liu; Hui Dong; Rui Li; Yaling Liu (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the selective loss of motor neurons. A bidirectional communication system known as the “microbiota-gut-brain” axis has a regulatory function in neurodegenerative disorders. The impact of probiotics on ALS through the “microbiota-gut-brain” axis remains uncertain. A longitudinal investigation was conducted to examine the alterations in the structure of the ileum and colon in mutant superoxide dismutase 1 (SOD1 G93A ) transgenic mice models of ALS by using immunofluorescence and Western blotting. Subsequently, the mice were administered a multistrain probiotic mixture (LBE) or vehicle orally, starting from 60 days of age until the terminal stage of the disease. The effects of these agents on the behavior, gut microbiota, microbial metabolites, and pathological processes of the spinal and intestine of SOD1 G93A mice were analyzed, with a focus on exploring potential protective mechanisms. SOD1 G93A mice exhibit various structural abnormalities in the intestine. Oral administration of LBE improved the proinflammatory response, reduced aberrant superoxide dismutase 1 (SOD1) aggregation, and protected neuronal cells in the intestine and spinal cord of SOD1 G93A mice. Furthermore, LBE treatment resulted in a change in intestinal microbiota, an increase in short-chain fatty acid levels, and an enhancement in autophagy flux. SOD1 G93A mice exhibited various structural abnormalities in the intestine. LBE can improve the proinflammatory response, reduce aberrant SOD1 aggregation, and protect neuronal cells in the spinal cord and intestine of SOD1 G93A mice. The positive effect of LBE can be attributed to increased short-chain fatty acids and enhanced autophagy flux.

Boosting seawater denitrification in an electrochemical flow cell - Ding Li; Shuang-Cheng Jiang; Jia-Fang Xie; Jian Zhang; Ying-Lian Zheng; Quan-Bao Zhao; Han-Qing Yu (Water Research, 2024)

Corrigendum to “Lepidium meyenii (Maca) polysaccharides mitigate liver toxicity of aflatoxin B1 through activation of NRF-2/GPX and AhR/STAT3 signaling pathways” [Toxicon, 250 (2024) 108117] - Jing Zhang; Zhen Peng; Dong Cheng; Wenhuan Yao; Hui Li; Qi Zhang; Ruisen Guo; Kunyan Li; Longrui Zou; Jia-Sheng Wang; Qiang Jia; Tianliang Zhang; et al. (Toxicon, 2024)

Lepidium meyenii (Maca) polysaccharides mitigate liver toxicity of aflatoxin B1 through activation of NRF-2/GPX and AhR/STAT3 signaling pathways - Jing Zhang; Zhen Peng; Dong Cheng; Wenhuan Yao; Hui Li; Qi Zhang; Ruisen Guo; Kunyan Li; Longrui Zou; Jia-Sheng Wang; Qiang Jia; Tianliang Zhang; et al. (Toxicon, 2024)

Air pollutants and the risk of incident hepatobiliary diseases: A large prospective cohort study in the UK Biobank - Bolun Cheng; Wenming Wei; Chuyu Pan; Li Liu; Shiqiang Cheng; Xuena Yang; Peilin Meng; Boyue Zhao; Jinyu Xia; Huan Liu; Yumeng Jia; Yan Wen; et al. (Science of The Total Environment, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Super-exchange interaction enables Fe2−xMnxO3 perovskite with excellent catalytic oxidation activity toward hexabromocyclododecane under humidity - Mingge Wu; Cheng Chen; Jia Duo; Qianqian Li; Maoyong Song; Bohua Sun; Guijin Su (Journal of Hazardous Materials, 2024)

Microbial inoculants using spent mushroom substrates as carriers improve soil multifunctionality and plant growth by changing soil microbial community structure - Hui Nie; Chong Li; Zhaohui Jia; Xuefei Cheng; Xin Liu; Qianqian Liu; Meiling Chen; Yong Ding; Jinchi Zhang (Journal of Environmental Management, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Pyrrole adducts mediated mitochondrial dysfunction activates SARM1-dependent axon degeneration in 2,5-hexanedione-induced neuropathy - Wenting Ni; Yihan Ye; Shuai Wang; Xianjie Li; Hui Li; Dong Cheng; Qiang Jia; Zhidan Liu; Shulin Shan; Yalong Qiang; Shihua Chao; Xiulan Zhao; et al. (Environmental Pollution, 2024)

Current regulates electron donors for heterotrophic and autotrophic microorganisms to enhance sulfate reduction in three-dimensional electrode biofilm reactors - Yang Liu; De-Zhuang Gao; Jia-Qi Fan; Yu-Chen Sun; Wei-Lei Jin; Jia-Cheng Li; Jie Deng; Juan Xu (Chemical Engineering Journal, 2024)

Conjugation-regulated lateral and stereoelectronic effects in single-molecule junctions - Xiao Wei; Xuanhao Cao; Jie Hao; Xinyue Chang; Ping Duan; Li Cheng; Keqiu Chen; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Chemical Engineering Journal, 2024)

Study on the effects of electrode volume fraction and electrode particle radius on dynamic electrochemical-thermal-aging coupling characteristics of lithium cell based on cylindrical cell design method - Xu-Dong Yuan; Zhen-Kai Xiong; Lian-Cheng Li; Chuan-Ye Tang; Qi-Wei Jia; Hong-Chuan Tuo; Yan Zhang (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Monthly Runoff forecasting using A Climate‑driven Model Based on Two-stage Decomposition and Optimized Support Vector Regression - Zhuo Jia; Yuhao Peng; Qin Li; Rui Xiao; Xue Chen; Zhijin Cheng (Water Resources Management, 2024)

Trifluoro-Icaritin Ameliorates Neuroinflammation Against Complete Freund’s Adjuvant-Induced Microglial Activation by Improving CB2 Receptor-Mediated IL-10/β-endorphin Signaling in the Spinal Cord of Rats - Guangsen Liu; Dandan Jia; Weiwei Li; Zhihua Huang; Reai Shan; Cheng Huang (Journal of Neuroimmune Pharmacology, 2024)

The first dimeric indole-diterpenoids from a marine-derived Penicillium sp. fungus and their potential for anti-obesity drugs - Hui-Fang Du; Lei Li; Ya-Hui Zhang; Xu Wang; Cheng-Yan Zhou; Hua-Jie Zhu; Charles U. Pittman; Jia-Wen Shou; Fei Cao (Marine Life Science & Technology, 2024)
Obesity has become a worldwide health problem. Seeking natural products with anti-obesity activity from lots of fungi has drawn the attention of pharmacologists. In our study, dipenipenoids A and B ( 1 and 2 ), the first dimeric indole-diterpenoids with a rare C-20–C-22′ linkage, and their monomers ( 3 and 4 ), were isolated from a marine-derived Penicillium sp. CF-06 fungus from Suaeda salsa . The absolute configurations of 1 – 3 were assigned by the calculated TDDFT ECD method. The structure of 4 was verified by a single-crystal X-ray diffraction method for the first time. Interestingly, 1 and 2 displayed significant effects on the differentiation of 3T3-L1 adipocytes by down-regulating the expression of peroxisome proliferator-activated receptor gamma (PPAR γ ) and CCAAT/enhancer binding protein alpha (C/EBP α ) proteins, while monomers 3 and 4 exhibited no activity. Molecular docking results explained the mechanism that the interaction between dimer 1 and PPAR γ was stronger than that between monomer 3 and PPAR γ . Our research could provide new insight for the discovery of anti-obesity drugs.

Associations between polychlorinated biphenyls and cancer risk among type 2 diabetes: The modifying effects of lifestyle - Peiwen Li; Yu Wang; Qianying Liu; Yan Yan; Zhuoya Zhao; Shiyang Zhang; Chengyong Jia; Jun An; Cheng Xu; Xin Zhang; Tao Jing; Huan Guo; et al. (Chemosphere, 2024)

Paleolatitude of Mafic Dykes in the Xiugugabu ophiolite: Implications for the intraoceanic Trans-Tethyan subduction zone and multistage India-Eurasia collision - Xingduo Ma; Xiaodong Tan; Yalin Li; Shuai Li; Zijian Li; Yongyong Jia; Siqi Xiao; Jianbo Cheng (Tectonophysics, 2024)

Machine learning for high-precision simulation of dissolved organic matter in sewer: Overcoming data restrictions with generative adversarial networks - Feng Hou; Shuai Liu; Wan-Xin Yin; Li-Li Gan; Hong-Tao Pang; Jia-Qiang Lv; Ying Liu; Hong-Cheng Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Classifying iron ore with water or dust adhesion combining differential feature and random forest using hyperspectral imaging - Jinbao Jiang; Cheng Nie; Jiushuai Deng; Kangning Li; Lixin Jia; Tiancheng Sun; Zezheng Li (Minerals Engineering, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

A novel LD-targeting cysteine-activated fluorescent probe for diagnosis of APAP-induced liver injury and its application in food analysis - Zhiqiang Yang; Xin Kang; Jia Li; Longxuan Li; Xiaoping Ye; Xiaoya Liu; Kun Chen; Yun Deng; Cheng Peng; Bo Ren; Zhixing Cao; Yuyu Fang (Food Chemistry, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Natural insect-derived Nanoparticle: An ultra-bright and instantaneous Labeled signal tag for green and efficient Immunochromatographic assay of chloramphenicol - Shaochi Wang; Ting Du; Huilin Jia; Wentao Zhang; Jing Sun; Daohong Zhang; Zhenyu Li; Jie Cheng; Jianlong Wang (Chemical Engineering Journal, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Boosting ferroptosis by intervention of redox balance and synergetic with photothermal/photodynamic therapy for suppression of pancreatic cancer - Yixun Jin; Jia Huang; Yuming Tang; Zengyue Li; Amin Zhang; Ziyun Yang; Jiani Song; Xinyang Huang; Yaya Bai; Chao Sun; Xuejiao Wu; Jin Cheng; et al. (Chemical Engineering Journal, 2024)

Mining Pressure Distribution Law and Disaster Prevention of Isolated Island Working Face Under the Condition of Hard “Umbrella Arch” - Chong Jia; Xingping Lai; Feng Cui; Haidong Xu; Suilin Zhang; Yuhang Li; Cheng Zong; Zhong Luo (Rock Mechanics and Rock Engineering, 2024)

Fine structure exploration and 3D quantitative evaluation model - Fangying Dong; Huiyong Yin; Wenju Cheng; Yongjie Li; Jiancong Fan; Haixiao Ding; Xiaorong Zhang; Chuanwei Jia (Bulletin of Engineering Geology and the Environment, 2024)

Overexpression of dehydroascorbate reductase gene IbDHAR1 improves the tolerance to abiotic stress in sweet potato - Qirui Cheng; Xuan Zou; Yuan Wang; Zhe Yang; Xiangpo Qiu; Sijie Wang; Yanxin Yang; Dongjing Yang; Ho Soo Kim; Xiaoyun Jia; Lingzhi Li; Sang-Soo Kwak; et al. (Transgenic Research, 2024)

Associations between exposure to brominated flame retardants and periodontitis in U.S. adults - Jia-jie Lv; Shu-yue Li; Xiang-meng Kong; Yan Zhao; Xin-yu Li; Hong Guo; Chu Feng; Cheng-hao Yang (Chemosphere, 2024)

Repose angle prediction of railway ballast based on Hopper Flow Test and PCA-Stacking ensemble learning method - Chen Xu; Yujie Zhu; Cheng Chen; Xibei Jia; Shaoshuo Li; Lei Zhang (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Avermectin induced vascular damage in zebrafish larvae: association with mitochondria-mediated apoptosis and VEGF/Notch signaling pathway - Wei-Guo Wang; Xu-Feng Jiang; Cheng Zhang; Xiu-Ping Zhan; Jia-Gao Cheng; Li-Ming Tao; Wen-Ping Xu; Zhong Li; Yang Zhang (Journal of Hazardous Materials, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Bensulfuron methyl induced multiple stress responses in the field wheat plants: Microbial community and metabolic network disturbance - Chunran Zhou; Dong Li; Peijuan Miao; Haiyan Cheng; Hui Zhang; Xiaoying Wan; Huan Yu; Yujiao Jia; Qinyong Dong; Canping Pan (Journal of Hazardous Materials, 2024)

Dual room temperature target controlof district heating substation based on room temperature detection - Zhiwei Li; Junjie Liu; Lizhi Jia; Yanmin Wang; Jian Zhang; Yan Li; Hongjuan Cheng (Energy and Buildings, 2024)

Nonlinear effect assessment for seismic ground motions of sedimentary basins based on deep neural networks - Jia-wei Zhao; Si-bo Meng; Zhong-xian Liu; Cheng-cheng Li; Kang Tang (Computers & Geosciences, 2024)

Preparation and design of intelligent multi-response PTMC/PVP composite nanofibrous dressing to promote wound closure and its applications in diabetic wounds - Liping Liu; Tao Yang; Shaoru Wang; Wenyuan Jia; Yun Liu; Kun Jiao; Yongzheng Yan; Yuheng Yang; Xuanzuo Jiang; Chiyu Li; Zhiqiang Cheng; Guomin Liu; et al. (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Two dwarfing genes Rht-B1b and Rht-D1b show pleiotropic effects on grain protein content in bread wheat (Triticum aestivum L.) - Wenjing Hu; Di Wu; Dongshen Li; Xiaoming Cheng; Zunjie Wang; Die Zhao; Jizeng Jia (Theoretical and Applied Genetics, 2024)

Mineral-Solubilizing Microbial Inoculums Promote Robinia Pseudoacacia L. Growth By Optimizing Rhizospheric Soil Microbial Community Structure - Zhaohui Jia; Chong Li; Shilin Ma; Xin Liu; Miaojing Meng; Xuefei Cheng; Hui Nie; Jinchi Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Molecular characterization of a sweetpotato stress tolerance-associated GDP-L-galactose phosphorylase gene (IbGGP1) in response to abiotic stress - Yanxin Yang; Sijie Wang; Qirui Cheng; Xuan Zou; Zhe Yang; Peng Li; Yuan Wang; Dongjing Yang; Ho Soo Kim; Xiaoyun Jia; Lingzhi Li; Sang-Soo Kwak; et al. (Plant Biotechnology Reports, 2024)

Microbial transformation mechanisms of particulate organic carbon to mineral-associated organic carbon at the chemical molecular level: Highlighting the effects of ambient temperature and soil moisture - Yali Niu; Yue Li; Mingxuan Lou; Zhen Cheng; Renjie Ma; He Guo; Jian Zhou; Hongtao Jia; Lichao Fan; Tiecheng Wang (Soil Biology and Biochemistry, 2024)

New therapeutic target NCF1-directed multi-bioactive conjugate therapies prevent preterm birth and adverse pregnancy outcomes - Juan Cheng; Xiaoyan Jia; Limei Yang; Siqi Zhang; Zhiyu Chen; Qian Gui; Ting Li; Zedan Pu; Hongbo Qi; Jianxiang Zhang (Science Bulletin, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Middle to Upper Ordovician stable carbon isotope stratigraphy and sedimentary facies in the Shunbei and Tahe areas, northern-central Tarim, China - Dong-Chen Ma; Wen-Jie Li; Zhong-Yang Chen; Xiang Fang; Jun-Feng Cheng; Xing-Liang Jia (Palaeoworld, 2024)

Effects of sulfite and freezing co-pretreatment on the volatile fatty acids production of waste activated sludge in anaerobic fermentation - Li-Li Yang; Yong Zhang; Hui Wang; Jian Huang; Yi-Fan Xiao; Jia-Qi Liu; Can Li; Ding-Cheng Hu; Chuan-Chuan Yan (Journal of Water Process Engineering, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Fe0-mediated mixotrophic denitrification enhanced by carbon fiber for secondary effluent with low C/N ratio - Yi-Mei Cheng; Lin-Chun Jia; Gang Xue; Xian-Ying Li (Journal of Environmental Chemical Engineering, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Isochlorogenic acid A ameliorated lead-induced anxiety-like behaviors in mice by inhibiting ferroptosis-mediated neuroinflammation via the BDNF/Nrf2/GPX4 pathways - Jun-Tao Guo; Han-Yu Li; Chao Cheng; Jia-Xue Shi; Hai-Nan Ruan; Jun Li; Chan-Min Liu (Food and Chemical Toxicology, 2024)

SfuPKS2, a novel type III polyketide synthase from Sargassum fusiforme, shows high substrate specificity - Jia-Min Xu; Yi-Cheng Xu; Chen-Xi Cheng; Dong-Sheng Zhao; Zhi-Wei Hu; Shu-Ming Li; Salah Fatouh Abou-Elwafa; Xiufeng Yan; Hui-Xi Zou; Nan Li (Journal of Applied Phycology, 2024)

Characterizing and identifying of miRNAs involved in berberine modulating glucose metabolism of Megalobrama amblycephala - Mingyang Liu; Chang He; Tingting Zhu; Xiaoyan Jia; Li Zhang; Weibo Jiang; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Hengtong Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Aridity-driven divergence in soil microbial necromass carbon in alpine grasslands of the Tibetan Plateau - Yunfei Zhao; Xia Wang; Yazhen Li; Menghan Yuan; Jia Li; Huawei Zhu; Zhuoyun Cheng; Wenhui Duan; Junwu Wang (Biology and Fertility of Soils, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

DNA Methylation is Involved in Sex Determination in Spinach - Keli Jia; Jiaming Duan; Guangqian Cheng; Heng Li; Shufen Li; Miao Hu (Biochemical Genetics, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Towards urban energy sustainability and resiliency through smart agriculture and effective renewable resource allocation - Lijun Cheng; Azurah Samah; Yubo Zhang; Zongwei Jia; Fuzhong Li (Sustainable Cities and Society, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Antiadhesive, antibacterial, and anti-inflammatory sandwich-structured ZIF8-containing gauze for enhanced wound healing - Xinghai Wu; Cheng Wang; Jia Wang; Yuchen Feng; Yunpeng Zhu; Yijia Pan; Yifan Yuan; Chenhui Chen; Junyan Cao; Jixing Lin; Xian Tong; Yuncang Li; et al. (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Formation of secondary organic aerosols from Cl-initiated oxidation of anisole: Rapid release of ultrafine particles and organic chlorides - Fashuai Pan; Jiaoyang Ma; Qianqian Yan; Gaosheng Zhao; Bin Jia; Li Xu; Ping Cheng (Atmospheric Environment, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

A Monte Carlo simulation-based health risk assessment of heavy metals in soils of the tropical region in southern China - Haoran Huang; Hang Su; Xiang Li; Yan Li; Yujie Jiang; Ke Liu; Xuefeng Xie; Zhenyi Jia; Huanchao Zhang; Genmei Wang; Zi Ye; Xinyu Cheng; et al. (Environmental Geochemistry and Health, 2024)

Overexpression of sweetpotato glutamylcysteine synthetase (IbGCS) in Arabidopsis confers tolerance to drought and salt stresses - Zhe Yang; Yuan Wang; Qirui Cheng; Xuan Zou; Yanxin Yang; Peng Li; Sijie Wang; Yue Su; Dongjing Yang; Ho Soo Kim; Xiaoyun Jia; Lingzhi Li; et al. (Journal of Plant Research, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Changes in soil aggregate stability and aggregate-associated carbon under different slope positions in a karst region of Southwest China - Shiwei Liu; Rutong Wang; Yan Yang; Weiyu Shi; Ke Jiang; Luyao Jia; Feng Zhang; Xian Liu; Lei Ma; Cheng Li; Pujia Yu (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Ultrathin Sn-doped Ga2O3 for power field-effect transistors: Si-compatible 4-inch array with high-k gate dielectric - Zi-Chun Liu; Jia-Cheng Li; Hui-Xia Yang; Han Yang; Yuan Huang; Yi-Yun Zhang; Pui-To Lai; Yuan-Xiao Ma; Ye-Liang Wang (Science Bulletin, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Modulating the acidity and reducibility of FeMn/TiO2 to boost the low-temperature selective catalytic reduction of NOx - Jingyi Zhu; Yuankai Shao; Zhenguo Li; Kaixiang Li; Xiaoning Ren; Lingfeng Jia; Huiquan Li; Huifang Cheng; Jian Liu; Jixing Liu (Fuel, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

Using untargeted metabolomics and GC-IMS to analysis the influence of fat distribution on the flavor formation of bacon - Yang Yufei; Li Pan; Cheng Jia; Wu Guofei; Ren Hongqiang; Wang Ling; Lu Hongzhao; Zeng Wenxian; Zhang Tao (Food Bioscience, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Forecasting urban air pollution using multi-site spatiotemporal data fusion method (Geo-BiLSTMA) - Tonghua Jia; Guangxu Cheng; Zhiteng Chen; Jiacong Yang; Yun Li (Atmospheric Pollution Research, 2024)

Sex differences of signal complexity at resting-state functional magnetic resonance imaging and their associations with the estrogen-signaling pathway in the brain - Cheng-li Zhao; Wenjie Hou; Yanbing Jia; Barbara J. Sahakian; Qiang Luo (Cognitive Neurodynamics, 2024)

Helicobacter pylori infection induces gastric cancer cell malignancy by targeting HOXA-AS2/miR-509-3p/MMD2 axis - Si Cheng; Yu Jia; Juan Wu; Jiguang Li; Yan Cao (Genes & Genomics, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Thermoexergetic analysis and response optimisation of selective exhaust gas recirculation with solvent-based CO2 capture in a natural gas-fired combined cycle power plant - Youning Tang; Cheng Tung Chong; Jo-Han Ng; Laura Herraiz; Jia Li; Hwai Chyuan Ong; Su Shiung Lam; Meisam Tabatabaei; William Woei Fong Chong (Clean Technologies and Environmental Policy, 2024)

Simultaneous and on-line detection of organic and heavy metal components in water using a novel nebulization-assisted injection plasma ionization triple quadruple mass spectrometry instrument - Gaosheng Zhao; Maolin Yang; Tingting Zhang; Bin Jia; Li Xu; Ping Cheng (Analytica Chimica Acta, 2024)

Three-dimensional printing and decellularized-extracellular-matrix based methods for advances in artificial blood vessel fabrication: A review - Bing Li; Yan Shu; Hailin Ma; Kun Cao; Yuen Yee Cheng; Zhilin Jia; Xiao Ma; Hongfei Wang; Kedong Song (Tissue and Cell, 2024)

Enhancing social vulnerability assessment with energy resilience: A comprehensive study of the Netherlands - Wen Song; Yinshuai Li; Jie Cheng; Ruishan Chen; Jun Wu; Nan Jia (Sustainable Cities and Society, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Seismic hazard models for typical urban masonry structures considering optimized regression algorithms - Si-Qi Li; Yi-Ru Li; Jia-Cheng Han; Peng-Fei Qin; Ke Du (Bulletin of Earthquake Engineering, 2024)

Alterations in degree centrality and functional connectivity in tension-type headache: a resting-state fMRI study - Shuxian Zhang; Mengqi Zhao; Jiazhang Sun; Jianjie Wen; Mengting Li; Chao Wang; Qinyan Xu; Jili Wang; Xihe Sun; Lulu Cheng; Xiaomeng Xue; Xizhen Wang; et al. (Brain Imaging and Behavior, 2024)

Enhancing fusarium head blight detection in wheat crops using hyperspectral indices and machine learning classifiers - Ghulam Mustafa; Hengbiao Zheng; Imran Haider Khan; Jie Zhu; Tao Yang; Aiguo Wang; Bowen Xue; Can He; Haiyan Jia; Guoqiang Li; Tao Cheng; Weixing Cao; et al. (Computers and Electronics in Agriculture, 2024)

Suppression of neutrophil extracellular traps is responsible for the amelioration of chemotherapeutic intestinal injury by the natural compound PEITC - Mei Bai; Shuaifei Li; Cui Zhang; Ning An; Jie Wang; Jia Qin; Rumeng Jia; Wentao Liu; Jingcai Cheng; Xuefeng Wu; Qiang Xu (Toxicology and Applied Pharmacology, 2024)

Enhancement of antioxidant quality by Bacillus siamensis N-1 and the role of LcPOD4 in regulating peel browning and senescence of litchi fruit - Xin Wang; Shicheng Zou; Nanpu Cheng; Wenjun Jia; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

Long-term ambient air pollution and the risk of musculoskeletal diseases: A prospective cohort study - Bolun Cheng; Chuyu Pan; Qingqing Cai; Li Liu; Shiqiang Cheng; Xuena Yang; Peilin Meng; Wenming Wei; Dan He; Huan Liu; Yumeng Jia; Yan Wen; et al. (Journal of Hazardous Materials, 2024)

Pyrolysis characteristics and kinetics of waste photovoltaic module: A TG-MS-FTIR study - Fan Li; Junyu Tao; Akash Kumar; Jia Zhang; Yunan Sun; Wei Guo; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Journal of Cleaner Production, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Adding a basis for sustainable poverty monitoring: The indicator systems and multi-source data of multi-dimensional poverty measurement - Xin Cheng; Yanting Liu; Ziyi Yu; Jingyue Gao; Yan Dai; Jia Chen; Yue Liu; Chaofan Wang; Chuanmin Shuai; Wenjing Li; Zhiju Xie (Environmental Development, 2024)

Reaction pathway of hydrothermal liquefaction of duckweed for wastewater treatment based on major model compounds - Yingying Yu; Kaige Zhao; Wanqing Li; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Junyu Tao; Xiaopeng Jia; Junhao Sun (Biomass and Bioenergy, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Therapeutic potential of dietary flavonoid hyperoside against non-communicable diseases: targeting underlying properties of diseases - Jia Xia; Yan Wan; Jiao-jiao Wu; Yu Yang; Jin-Feng Xu; Li Zhang; Dong Liu; Lu Chen; Fei Tang; Hui Ao; Cheng Peng (Critical Reviews in Food Science and Nutrition, 2024)

Extracting visual navigation line between pineapple field rows based on an enhanced YOLOv5 - Tian-Hu Liu; Yan Zheng; Jia-Shang Lai; Yi-Feng Cheng; Si-Yuan Chen; Bao-Feng Mai; Ying Liu; Jia-Yi Li; Zhong Xue (Computers and Electronics in Agriculture, 2024)

The effect of dietary vitamin A supplementation on growth, gonadal development, molting, immunity, and ammonia nitrogen resistance in sub-adult male Chinese mitten crab, Eriocheir sinensis - Weibo Jiang; Xiaoyan Jia; Maorong Zhang; Wei Qiang; Xiaoxue Shen; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

NaH2PO4 synergizes with organic matter to stabilize chromium in tannery sludge - Ruijie Ge; Tao E; Ying Cheng; Yuanfei Wang; Jia Yu; Yun Li; Shuyi Yang (Journal of Environmental Management, 2024)

Surface defect engineering of porous Ov-CeO2/Bi5O7I nanoflowers with Z-scheme heterojunction for efficient photocatalytic removal of mercury - Xin Zhang; Zhanwei Qiao; Jiang Wu; Tao Jia; Cheng Peng; Fengting Li; Qizhen Liu; Xiaokun Li; Zijian Xiang; Yuan Gao (Journal of Environmental Chemical Engineering, 2024)

Enhanced and accelerated degradation of PFOA using visible light—Applying semiconductor carbon nitride as an accelerator - Juying Li; Ying Liu; Yiqian Song; Li Cao; Yezhi Dou; Jia Yu; Yueqing Zhang; Jian He; Wei Dai; Cheng Yao; Deyang Kong (Journal of Environmental Chemical Engineering, 2024)

Micro(nano)plastics in marine medaka: Entry pathways and cardiotoxicity with triphenyltin - Ling Liu; Ren-Yan Du; Ruo-Lan Jia; Jin-Xin Wang; Cheng-Zhuang Chen; Ping Li; Ling-Ming Kong; Zhi-Hua Li (Environmental Pollution, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Comparative Proteomics Analysis Reveals the Molecular Mechanisms Underlying the Accumulation Difference of Bioactive Constituents in Taxilli Herba from Two Hosts - Jiahuan Yuan; Nan Wu; Wei Yang; Zhichen Cai; Cuihua Chen; Yongyi Zhou; Haijie Chen; Jia Xue; Xunhong Liu; Wenxin Wang; Jianming Cheng; Li Li (Journal of Plant Growth Regulation, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Paddy cultivation in degraded karst wetland soil can significantly improve the physiological and ecological functions of carbon-fixing resident microorganisms - Weihua Kang; Yutian Xiao; Wei Li; Aoqi Cheng; Congyu Cheng; Zhongjun Jia; Longjiang Yu (Science of The Total Environment, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Combining with volatilomic profiling and chemometrics to explore the volatile characteristics in five different dried Zanthoxylum bungeanum maxim - Jinze Feng; Lifang Hao; Haobin Zhu; Maoying Li; Yulin Liu; Qiuxiao Duan; Lili Jia; Dongmei Wang; Cheng Wang (Food Research International, 2024)

The role of oxide supports in constructing plasma-treated gold nanocatalysts for visible light photocatalytic oxidation of CO - Bin Zhu; Chong-Hua Zhong; Bang-You Jia; Tie Li; Jing-Lin Liu; Ye-Cheng Li; Yi-Min Zhu (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Evolution law of wind-sand flow field of multi-row reed sand barriers and optimal spacing - Yuanfeng An; Jianjun Cheng; Lusheng Ding; Boyu Chen; Li Gao; Jia Lei; Benteng Ma; Zhipeng Zhen (Natural Hazards, 2024)

Air particulate pollution exposure associated with impaired cognition via microbiota gut-brain axis: an evidence from rural elderly female in northwest China - Jia Yuan; Hui Tan; Yue Cheng; Xinxin Ma; Sijin Jiang; Xinyao Hou; Shaoru Li; Lu Shi; Pu Li; Hongmei Xu; Jia Lv; Bei Han (Environmental Science and Pollution Research, 2023)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Harmonization of semi-objective ANP with explained CRITIC for quantitative evaluation of fire hazard risks for flame-retardant materials - Bin Zou; Xin Wang; Jiajun Li; Zhenfeng Cheng; Guotao Ye; Wenhao Yang; Liangyuan Qi; Pengfei Jia; Fukai Chu; Zetao Xiao; Lei Song; Zhou Gui; et al. (Process Safety and Environmental Protection, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Predicting TFe content and sorting iron ores from hyperspectral image by variational mode decomposition-based spectral feature - Cheng Nie; Jinbao Jiang; Jiushuai Deng; Kangning Li; Lixin Jia; Tiancheng Sun (Journal of Cleaner Production, 2023)

Cinnamon essential oil Pickering emulsions: Stabilization by bacterial cellulose nanofibrils and applications for active packaging films - Xiaotong Qin; Bo Li; Li Li; Fengping Wang; Shiru Jia; Yanyan Xie; Cheng Zhong (Food Bioscience, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Ultra-fast degradation of ciprofloxacin by the peroxymonosulfate activation using a Co/Al-LDH decorated magnetic hydrochar: Structural design, catalytic performance and synergistic effects - Jian Zhang; Jia-Fang Xie; Jia-Cheng E. Yang; Ding Li; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2023)

From cellulose to tar: Analysis of tar formation pathway with distinguishing the primary and secondary reactions - Xiaopeng Jia; Yuechi Che; Jian Li; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Juan Zhao (Bioresource Technology, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Incidence and risk factors of drug-induced kidney injury in children: a systematic review and meta-analysis - Miao Zhang; Bingchen Lang; Hailong Li; Liang Huang; Linan Zeng; Zhi-Jun Jia; Guo Cheng; Yu Zhu; Lingli Zhang (European Journal of Clinical Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Analysis of leaf economics sheds light on the heterophylly and ecological strategies of Paleocene Ginkgo leaves from Henan Province, China - Qijia Li; Bingshan Niu; Yusheng (Christopher) Liu; Hui Jia; Yu Li; Li Xu; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Nitrogen removal performance and C, N, S transformation under dry-wet alterations of heterotrophic-autotrophic sequential bioretention system amended with waste reed and sulfur - Zhaoying Liu; Liyuan Wu; Yang Hao; Yu Cheng; Chaohong Tan; Jia Wang; Haiyan Li (Journal of Cleaner Production, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Circulating organochlorine pesticide levels, genetic predisposition and the risk of incident type 2 diabetes - Chengyong Jia; Shiyang Zhang; Xu Cheng; Peiwen Li; Jun An; Xin Zhang; Wending Li; Yali Xu; Handong Yang; Tao Jing; Huan Guo; Meian He (Environmental Pollution, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Scalable wet-spinning of wearable chitosan-silica textile for all-day radiative cooling - Cheng Chen; Xiaoyu Jia; Xiaorui Li; Mingyang Shi; Jiayi Hu; Mengyao Song; Shuwang Wu; Hongliang Dai; Xingang Wang; Hongya Geng (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Ecological vulnerability of China’s Yellow River Basin: evaluation and socioeconomic driving factors - Xiaorui Wang; Liangrong Duan; Tianjiao Zhang; Wen Cheng; Qi Jia; Jiangsu Li; Mingyue Li (Environmental Science and Pollution Research, 2023)

Spatial distribution and influencing factors of China’s household biogas: evidence from provincial-level data - Zhenghao Liang; Chaojie Lan; Xin Jin; Shoupeng Li; Jinwen Cai; Shuyun Yang; Guangqing Hou; Wenxiao Cheng; Xujie Shao; Ruihong Jia; Jingang Ye; Dairen Shi; et al. (Environmental Science and Pollution Research, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Community resilience in city emergency: Exploring the roles of environmental perception, social justice and community attachment in subjective well-being of vulnerable residents - Qian-Cheng Wang; Xuan Liu; Izzy Yi Jian; En-Jia Zhang; Yu-Ting Hou; Kin Wai Michael Siu; Yi-Bin Li (Sustainable Cities and Society, 2023)

Fire effects on soil carbon cycling pools in forest ecosystems: A global meta-analysis - Yue Cheng; Peng Luo; Hao Yang; Honglin Li; Chuan Luo; Honghong Jia; Yu Huang (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

Research on the purification enhancement of ecological ponds: Integrating water cycle optimization and plants layout - Xiangdong Pan; Shengyun Liu; Ran Li; Hailong Sun; Jingjie Feng; Xiaolong Cheng; Jia Yao (Journal of Environmental Management, 2023)

Insights on the dual role of low-rank coal with high mineral catalysis index (LRC-HMCI) during blending coal for activated carbon production and low-temperature NH3-SCR of NO - Jian Niu; Jizhen Jia; Huirong Zhang; Yanxia Guo; Linbo Li; Fangqin Cheng (Fuel, 2023)

Development of a recurrent spatiotemporal deep-learning method coupled with data fusion for correction of hourly ozone forecasts - Jie Li; Ji-cheng Jang; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Jia Xing; Xinyi Dong; Jinying Li; Bin Zhao; Bingyao Zhang; Yingzhi Yuan (Environmental Pollution, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the mechanism of the effect of perfluorocaproic acid exposure on brain injury in Carassius auratus - Xue Jiao; Zheng yao Guo; Jia Sun; Cheng Bi; Ai-dong Qian; Yue-hong Li (Aquatic Toxicology, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

A two-step non-nominal troposphere monitor for GBAS - Jiaxiang Li; Hao Yin; Jianhua Cheng; Liang Li; Chun Jia; Jiachang Jiang (GPS Solutions, 2023)

Enhancement of chiral drugs separation by a novel adjustable gravity mediated capillary electrophoresis combined with sulfonic propyl ether β-CD polymer - Yaqin Nan; Pingyi Zheng; Mengqi Cheng; Ran Zhao; Haijiao Jia; Qinggang Liang; Youxin Li; James J. Bao (Analytica Chimica Acta, 2023)

Assessment of 13 essential and toxic trace elements in tumor and peritumoral brain tissues from human glioblastoma - Hao-Long Zeng; Binmei Jia; Qing Yang; Fengbo Zeng; Huijun Li; Chao-Xi Li; Liming Cheng (JBIC Journal of Biological Inorganic Chemistry, 2023)

Association of urinary heavy metal combined exposure with periodontitis among US adults from NHANES 2011–2014 - Zhen-Hua Li; Jiong Li; Yi-Cheng Mao; Jia-Wen Zhao; Hui-Yu Hu; Sun Zhang; Zhe-Ye Liu; Xue-Jie Liu; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Science and Pollution Research, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Isochlorogenic acid B alleviates lead-induced anxiety, depression and neuroinflammation in mice by the BDNF pathway - Jia-Xue Shi; Chao Cheng; Hai-Nan Ruan; Jun Li; Chan-Min Liu (NeuroToxicology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

A new insight of water inrush mode and coal (rock) pillars setting in near-fault mining under high confined water - Fangying Dong; Huiyong Yin; Qingfu Feng; Shuo Li; Wei Zhou; Wenju Cheng; Mei Qiu; Yongli Shi; Chuanwei Jia (Journal of Applied Geophysics, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Tracing the nitrogen nutrient status of crop based on solar-induced chlorophyll fluorescence - Yuming Yin; Jie Zhu; Xinwen Xu; Min Jia; Timothy A. Warner; Xue Wang; Tongjie Li; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (European Journal of Agronomy, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Formation of secondary organic aerosols from the ozonolysis of Cis-3-hexenyl acetate: The effect of acidic seed particles and SO2 - Dalin Shi; Yi Chen; Jixing Liu; Gaosheng Zhao; Li Xu; Bin Jia; Ping Cheng (Atmospheric Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

PPARɑ Ligand Caudatin Improves Cognitive Functions and Mitigates Alzheimer’s Disease Defects By Inducing Autophagy in Mice Models - Senthilkumar Krishnamoorthi; Ashok Iyaswamy; Sravan Gopalkrishnashetty Sreenivasmurthy; Abhimanyu Thakur; Karthick Vasudevan; Gaurav Kumar; Xin-Jie Guan; Kejia Lu; Isha Gaurav; Cheng-Fu Su; Zhou Zhu; Jia Liu; et al. (Journal of Neuroimmune Pharmacology, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Effect of gaseous pollutant and greenness exposure on mortality during treatment of newly treated tuberculosis patients: a provincial population-based cohort study - Jia-Wen Zhao; Xin-Qiang Wang; Zhen-Hua Li; Yi-Cheng Mao; Sun Zhang; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang; Xiao-Hong Kan (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Life cycle environmental and cost assessment of prefabricated components manufacture - Ziyue Cheng; Tianzuo Zhang; Xinying Zhou; Ziheng Li; Yuke Jia; Ke Ren; Tianshu Xu; Changting Li; Jinglan Hong (Journal of Cleaner Production, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Mn-MOF derived manganese sulfide as peroxymonosulfate activator for levofloxacin degradation: An electron-transfer dominated and radical/nonradical coupling process - Xiaolin Han; Wei Zhang; Shuai Li; Congyu Cheng; Qi Yu; Qilong Jia; Lei Zhou; Guangli Xiu (Journal of Environmental Sciences, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

Improvement in bacterial cellulose production by co-culturing Bacillus cereus and Komagataeibacter xylinus - Wenchao Li; Xinxin Huang; Huan Liu; Hao Lian; Bin Xu; Wenjin Zhang; Xuewen Sun; Wei Wang; Shiru Jia; Cheng Zhong (Carbohydrate Polymers, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Nitric oxide induces defense responses in apple fruit against black spot disease caused by Alternaria alternata - Jie Han; Yingying Fan; Shicui Li; Binxin Jia; Jin Yang; Aibin Shen; Ting Dai; Jing An; Fengjuan Liu; Cheng Wang (South African Journal of Botany, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Selective flotation separation of hemimorphite from quartz using the biosurfactant sodium N-lauroylsarcosinate as a novel collector - Kai Jia; Yuhang Lu; Jiang Liu; Shun Cheng; Shiqiang Liu; Yijun Cao; Guosheng Li (Minerals Engineering, 2023)

Association between polychlorinated biphenyls exposure and incident type 2 diabetes mellitus: A nested case-control study - Peiwen Li; Yali Xu; Zhaoyang Li; Xu Cheng; Chengyong Jia; Shiyang Zhang; Jun An; Xin Zhang; Yan Yan; Meian He (Environmental Research, 2023)

Changes in soil organic carbon stability in association with microbial carbon use efficiency following 40 years of afforestation - Qianxi Li; Wei Jia; Junjun Wu; Lingling Wang; Feng Huang; Xiaoli Cheng (CATENA, 2023)

Carbon-containing additives changes the phosphorus flow by affecting humification and bacterial community during composting - Shuxin Li; Shaoqi Xu; Shuo Chen; Hao Zhang; Yabin Zhan; Kaixue Jia; Meidi Cheng; Yuquan Wei (Bioresource Technology, 2023)

Population pharmacokinetic analyses of tacrolimus in non-transplant patients: a systematic review - Cheng-Bin Wang; Yu-jia Zhang; Ming-Ming Zhao; Li-mei Zhao (European Journal of Clinical Pharmacology, 2023)

Performance and mechanism of simultaneous Sb(III) and Cd(II) removal from water by Fe–Mn binary oxide/bone char - Xiaolin Han; Congyu Cheng; Wei Zhang; Shuai Li; Qilong Jia; Guangli Xiu (Environmental Science and Pollution Research, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Influence analysis of overlying soil layer to seismic behavior of inclined liquefiable soil and pile interaction system - Xiao-ling Zhang; Li-jing Fang; Cheng-shun Xu; Ke-min Jia; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Role of macrophage AHR/TLR4/STAT3 signaling axis in the colitis induced by non-canonical AHR ligand aflatoxin B1 - Liwen Zhang; Dong Cheng; Jing Zhang; Hui Tang; Fenghua Li; Yi Peng; Xinglan Duan; En Meng; Cuili Zhang; Tao Zeng; Fuyong Song; Jia-Sheng Wang; et al. (Journal of Hazardous Materials, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Study on the hydraulic parameter differences between pumping and recharge in a confined aquifer of a soft soil area - Gang Zheng; Qinghan Li; Xuesong Cheng; Xiaomin Liu; Jianwei Jia; Ying Jiao; Da Ha (Hydrogeology Journal, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Rapid change of erosion-deposition evolution in the Minjiang estuary, Southeast China - Xiaohe Lai; Yuebao Hou; Jianping Jia; Cheng Chen; Yan Su; Jun Jiang; Jing Chen; Maotian Li; Yan Liu (Ocean & Coastal Management, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Adenosine triphosphate induced transition-metal phosphide nanostructures encapsulated with N, P-codoped carbon toward electrochemical water splitting - Peng Wei; Xueping Sun; Zhimin He; Fangyuan Cheng; Jia Xu; Qing Li; Yurong Ren; Jianhua He; Jiantao Han; Yunhui Huang (Fuel, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Impacts of climate change on vicennial spatial behaviors of Trichiurus japonicus in the East China Sea - Yan Jin; Xing-Wei Yuan; Yi Zhang; Jian-sheng Li; Li-ping Yan; Zun-lei Liu; Jia-hua Cheng (Estuarine, Coastal and Shelf Science, 2023)

Importance of amylose chain-length distribution in determining starch gelatinization and retrogradation property of wheat flour in the presence of different salts - Enpeng Li; Jiaqi Lv; Dongao Huo; Bin Jia; Cheng Li (Carbohydrate Polymers, 2023)

Phosphorus transformation behavior and phosphorus cycling genes expression in food waste composting with hydroxyapatite enhanced by phosphate-solubilizing bacteria - Shaoqi Xu; Kaixue Jia; Yi Zheng; Wenjie Chen; Zhigang Wang; Dan Wei; Baoru Sun; Meidi Cheng; Beibei Fan; Ji Li; Yuquan Wei (Bioresource Technology, 2023)

Rock Adaptability of TBM Variable Cross-section Cutter Ring Based on Finite Element Simulation - Jia-Li Zhao; Xian-Yong Zhu; Cheng Jiang; Song Yang; Xiong Xiao (Rock Mechanics and Rock Engineering, 2023)

An annually laminated stalagmite from the eastern Qinghai-Tibetan Plateau provides evidence of climate instability during the early MIS5e in the Asian summer monsoon - Tao Gao; Pingzhong Zhang; Hai Cheng; Leilei Zhang; Xinhu Li; Hongyu Shi; Wei Jia; Youfeng Ning; Hanying Li; R. Lawrence Edwards (Science China Earth Sciences, 2023)

Histone methyltransferase SETDB1 promotes osteogenic differentiation in osteoporosis by activating OTX2-mediated BMP-Smad and Wnt/β-catenin pathways - Lianying Hu; Zhen Cheng; Lunan Wu; Liangliang Luo; Ping Pan; Shujin Li; Qiyu Jia; Ning Yang; Bin Xu (Human Cell, 2023)

Contamination characteristics, spatial distribution and ecological-health risk assessment of legacy and current-use pesticides: a case study in the Beibu Gulf - Li Zhang; Jiaxin Ma; Peipei Liu; Anxiang Qi; Haiyan Jin; Renming Jia; Zhenming Zheng; Cheng Yan; Minghong Cai (Frontiers in Marine Science, 2023)
With the prohibition of conventional organochlorine pesticides (OCPs), the extensive use and continuous release of current-use pesticides (CUPs), such as organic amine pesticides (OAPs) and organophosphate pesticides (OPPs), in agriculture and mariculture activities have raised global attention. In this study, the occurrence and distribution of 36 pesticides from above 3 categories were investigated in seawater and sediment in Beibu Gulf, a typical subtropical agricultural and maricultrual zone. Results showed that pesticides were widely present in this region with the total concentration ranging from 0.36 to 21.07 ng/L in seawater and from 0.02 to 9.73 ng/g dw in sediment. OAPs and OPPs were the most abundant categories contributing 74% and 66% to the total pesticides burden in seawater and sediment, respectively, revealing the current-use pesticides as substitutes of legacy organochlorine pesticides (OCPs) were mainly used in surrounding areas. For both seawater and surface sediment, the spatial distribution of pesticides concentrations showed generally seaward decreasing trends, suggesting that anthropogenic activities at coastal areas have an important impact on pesticides pollution. Source identification indicated OCPs in some seawater samples might be from mixture of antifouling paint and dicofol usage, while history residues are main sources of OCPs in sediment. OAPs, especially for cyflufenamid and kresoxim-methyl, mainly come from agricultral and maricultural sewage input, and OPPs were speculated from currency transportation from surrounding areas. Ecological risk assessment showed that OPPs posed moderate to even high risks in most seawater sites. It appears that crustaceans are the most sensitive trophic species to OPPs among aquatic organisms, followed by fish. According to the results of health risks proposed by the major aquatic products in Beibu Gulf (fish and shrimp), the selected pesticides pose no health risk to humans. Nevertheless, OCPs made the highest contribution to the total HQ values. Comprehensively considering the evaluation results of both ecological and health risks, more attention should be given on OPPs and OCPs pollution in the Beibu Gulf.

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Two new dicyclic C-geranylflavanones isolated from Paulownia fortunei and their cytotoxicity - Wei-guo Liu; Cheng-mei Xiao; Jun Li; Su-ying Wu; Wen-chao Zhang; Ling-tao Kong; Wen-Zhao Tang; Xian-hui Jia (Phytochemistry Letters, 2023)

Seismic response study of a steel lattice transmission tower considering the hysteresis characteristics of bolt joint slippage - Jia-Xiang Li; Jin-Peng Cheng; Chao Zhang; Chun-Xu Qu; Xiao-Hong Zhang; Wen-Qiang Jiang (Engineering Structures, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Elucidating pollution characteristics, temporal variation and source origins of carbonaceous species in Xinxiang, a heavily polluted city in North China - Huanjia Liu; Mengke Jia; Jie Tao; Dan Yao; Juexiu Li; Ruiqin Zhang; Lanqing Li; Mengyuan Xu; Yujuan Fan; Yongli Liu; Ke Cheng (Atmospheric Environment, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Spatial confinement-based Figure-of-Eight nanoknots accelerated simultaneous detection and imaging of intracellular microRNAs - Huo Xu; Yanhui Zheng; Xiaojun Fang; Yinghao Cheng; Jianguo Xu; Jie Wang; Hongxia Li; Lee Jia; Chang Xue (Analytica Chimica Acta, 2023)

Hydroquinone triggers pyroptosis and endoplasmic reticulum stress via AhR-regulated oxidative stress in human lymphocytes - Xiaohan Yang; Shuangyan Dong; Chao Li; Ming Li; Caihong Xing; Jin He; Cheng Peng; Hua Shao; Qiang Jia (Toxicology Letters, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Interfacial composition in infant formulas powder modulate lipid digestion in simulated in-vitro infant gastrointestinal digestion - Xiaoxue Yu; Wenli Zhou; Zhibing Jia; Lu Liu; Xiaodong Li; Xiuxiu Zhang; Jinju Cheng; Chunli Ma; Lina Sun; Yang Jiao (Food Research International, 2023)

Effects of driving factors at multi-spatial scales on seasonal runoff and sediment changes - Guoce Xu; Yuting Cheng; Chaozhi Zhao; Jinsha Mao; Zhanbin Li; Lu Jia; Yixin Zhang; Bin Wang (CATENA, 2023)

Optical bulk-boundary dichotomy in a quantum spin Hall insulator - Junfeng Han; Pengcheng Mao; Hailong Chen; Jia-Xin Yin; Maoyuan Wang; Dongyun Chen; Yongkai Li; Jingchuan Zheng; Xu Zhang; Dashuai Ma; Qiong Ma; Zhi-Ming Yu; et al. (Science Bulletin, 2023)

Phytotoxic meroterpenoids with herbicidal activities from the phytopathogenic fungus Pseudopestalotiopsis theae - Dong Gan; Jia-Qi Liu; Yu-Jun Yang; Cheng-Yao Wang; Li Zhu; Chen-Zhe Li; Le Cai; Zhong-Tao Ding (Phytochemistry, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Tele-connection of global agricultural land network: Incorporating complex network approach with multi-regional input-output analysis - Mengyao Cheng; Jialu Wu; Chaohui Li; Yuanxin Jia; Xiaohua Xia (Land Use Policy, 2023)

Differences in watershed evaporation indicated by hydrogen and oxygen single and dual isotopes: Evidence from controlled simulation tests under different land uses - Yundi Hu; Hongdai Fan; Min Zhao; Deyong Hu; Qian Bao; Cheng Zeng; Dong Li; Yi Zhang; Fan Xia; Xianli Cai; Jia Chen; Zhongfa Zhou (Journal of Hydrology, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

NIR-responsive hollow germanium nanospheres mediate photothermal/photodynamic therapy and restrain immunosuppression to cooperatively eradicate primary and metastatic tumors - Qilin Li; Huiling Fan; Yunruo Xu; Miaodeng Liu; Jia Liu; Luming Xu; Meizhen Zou; Qian Cheng; Yan Zhang; Tao Liang; Lin Shi; Xianluo Hu; et al. (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Mechanism and stability of low cadmium accumulation in grafted soybeans induced by rootstocks - Lizong Sun; Chunyun Jia; Chenyang Xue; Cheng Guo; Xiaojun Li; Peidong Tai (Plant and Soil, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

Regeneration mechanism of a novel high-performance biochar mercury adsorbent directionally modified by multimetal multilayer loading - Li Jia; Peng Cheng; Yue Yu; Shi-hu Chen; Chen-xing Wang; Ling He; Hao-tian Nie; Jian-cheng Wang; Jian-chun Zhang; Bao-guo Fan; Yan Jin (Journal of Environmental Management, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus - Jianbo Zheng; Yongyi Jia; Fei Li; Meili Chi; Shun Cheng; Shili Liu; Wenping Jiang; Yinuo Liu (Fish & Shellfish Immunology, 2023)

Genome and transcriptome of Chinese medaka (Oryzias sinensis) and its uses as a model fish for evaluating estrogenicity of surface water - Yue Wang; Jilong Guo; Xiaojing Jia; Xiaozhe Luo; Ying Zhou; Xingtai Mao; Xiaolin Fan; Hongxia Hu; Hua Zhu; Chengxia Jia; Xuan Guo; Lan Cheng; et al. (Environmental Pollution, 2023)

Molten salt-induction of geometrically deformed ruthenium single atom catalysts with high performance for aerobic oxidation of alcohols - Xiuli Dong; Yufei Jia; Mingyang Zhang; Siqi Ji; Leipeng Leng; J. Hugh Horton; Chang Xu; Cheng He; Qiang Tan; Jiangwei Zhang; Zhijun Li (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

Study on spatio-temporal variation and hydrological connectivity of tidal creek evolution in Yancheng coastal wetlands - Shiwei Zhou; Cheng Wang; Yufeng Li; Wanchun Huang; Yue Jia; Yuqing Wang; Wei Xu; Chunqi Qiu; Hongyu Liu (Environmental Science and Pollution Research, 2022)

Application of biochar and compost improved soil properties and enhanced plant growth in a Pb–Zn mine tailings soil - Yizhi Cheng; Xuan Bu; Jing Li; Zhihui Ji; Chenggang Wang; Xiao Xiao; Fenglin Li; Zhuo-hui Wu; Guanxiong Wu; Pu Jia; Jin-tian Li (Environmental Science and Pollution Research, 2022)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Trace element signature of hydrothermal quartz: a potential tracer for ore genesis - Juan Dong; Li-Bin Jia; Mei-jia Song; Shu-Teng Xu; Mao-Wen Yuan; Cheng-Lu Li; Yuan-Jiang Yang (Arabian Journal of Geosciences, 2022)

Joint inversion method of formation shear-wave anisotropy from logging-while-drilling acoustic data - Jia-Cheng Li; Xiao He; Jiang Can (Applied Geophysics, 2022)

Abundant and diverse endophytic bacteria associated with medicinal plant Arctium lappa L. and their potential for host plant growth promoting - Jia-Qi Liu; Shu-Mei Chen; Chun-Mei Zhang; Ming-Jie Xu; Ke Xing; Cheng-Guo Li; Kui Li; Yu-Qin Zhang; Sheng Qin (Antonie van Leeuwenhoek, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Chemical constituents from the aerial part of Polygala tenuifolia - Yan-Gang Cheng; Jin-Yan Tan; Jian-Li Li; Shi-Hui Wang; Kai-Li Liu; Jia-Min Wang; Ying-Li Wang (Natural Product Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Combination of Se-methylselenocysteine, D-α-tocopheryl succinate, β-carotene, and l-lysine can prevent cancer metastases using as an adjuvant therapy - Yunlong Cheng; Shu Lian; Shuhui Li; Yusheng Lu; Jie Wang; Xiaoxiao Deng; Shengyi Zhai; Lee Jia (Journal of Zhejiang University-SCIENCE B, 2022)

Nutritional Components, Biochemical Characteristics, Enzyme Activities, and Growth Differences of Five Freshwater Fish Species? - Xiaona Jiang; Yan Li; Jingwen Tian; Chitao Li; Yanlong Ge; Xuesong Hu; Lei Cheng; Xiaodan Shi; Lianyu Shi; Zhiying Jia (Fishes, 2022)
Common carp (Cyprinus carpio) is an economically important fish worldwide, with many of its species bred for consumption. However, there are few reports on the comprehensive comparative analysis of the muscle nutritional quality and stress resistance characteristics of different common carp species. In this study, after 15 months of feeding in the same environment, the nutritional components, serum biochemical indices, liver antioxidant and intestinal digestive enzyme activities, and muscle growth-related gene expression were determined in Songpu mirror carp (SPM; Cyprinus carpio Songpumirror), Heilongjiang wild carp (HLJ; Cyprinus carpio haematopirus), cold-resistant strain of purse red carp (CPR; Cyprinus carpio ‘Red purse cold-resistant’), Songhe carp (SH; Cyprinus carpio ‘Songhe’), and Songpu carp (SP; Cyprinus carpio Songpu). Muscle nutrient composition showed that HLJ had a significantly lower crude fat content and higher docosahexaenoic acid (DHA) + eicosapentaenoic acid (EPA) proportion than the other four common carp species (p

DRAXIN as a Novel Diagnostic Marker to Predict the Poor Prognosis of Glioma Patients - Yulong Jia; Zhendong Liu; Xingbo Cheng; Runze Liu; Pengxu Li; Defu Kong; Wenjia Liang; Binfeng Liu; Hongbo Wang; Xingyao Bu; Yanzheng Gao (Journal of Molecular Neuroscience, 2022)
An increasing number of evidences have shown that the carcinogenic effect of DRAXIN plays an important role in the malignant process of tumors, but the mechanism of its involvement in glioma has not yet been revealed. The main aim of this study is to explore the relationship between DRAXIN and the prognosis and pathogenesis of glioma through a large quality of data analysis. Firstly, thousands of tissue samples with clinical information were collected based on various public databases. Then, a series of bioinformatics analyses were performed to mine data from information of glioma samples extracted from several reputable databases to reveal the key role of DRAXIN in glioma development and progression, with the confirmation of basic experiments. Our results showed that high expression of the oncogene DRAXIN in tumor tissue and cells could be used as an independent risk factor for poor prognosis in glioma patients and was strongly associated with clinical risk features. The reverse transcription-quantitative PCR technique was then utilized to validate the DRAXIN expression results we obtained. In addition, co-expression analysis identified, respectively, top 10 genes that were closely associated with DRAXIN positively or negatively. Finally, in vitro experiments demonstrated that knockdown of DRAXIN significantly inhibited proliferation and invasion of glioma cell. To sum up, this is the first report of DRAXIN being highly expressed in gliomas and leading to poor prognosis of glioma patients. DRAXIN may not only benefit to explore the pathogenesis of gliomas, but also serve as a novel biological target for the treatment of glioma.

Livin promotes Th2-type immune response in airway allergic diseases - Yue Wang; Zhiyu Xiang; Miaomiao An; Huijing Jia; Chunyan Bu; Yanfeng Xue; Yao Wei; Ruiying Li; Xueping Qi; Fengli Cheng; Changqing Zhao; Jinmei Xue; et al. (Immunologic Research, 2022)
Objectives To investigate the effects of livin on the Th2 immune response in airway allergic diseases (AAD) and explore the interaction among livin, GATA3, IL-4 in peripheral blood CD4 + T cells of AAD patients. Methods WT mice and livin KO mice were developed for model of AAD. Th2 cell levels in the lung tissues and spleen were assessed by flow cytometry. Also, it was assessed in the culture after exposing to livin inhibitor (Lp-15); the protein and mRNA levels of livin, GATA3 and IL-4 in peripheral blood CD4 + T cells isolated from patients with or without AAD were measured by real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting, respectively. Finally, Co-immunoprecipitation (Co-IP) was employed to identify the interaction between livin and GATA3. Results Compared with WT mouse, Th2 cell frequency in lung tissues and spleen was significantly decreased in livin KO mouse; after adding Lp-15, the differentiation from Naive CD4 + T cells in spleen to Th2 cells was blocked; the protein and mRNA levels of livin, GATA3 and IL-4 in AAD group were higher than that in control group. The levels of livin were positively correlated with IL-4, and GATA3 was also positively correlated with IL-4 and livin. GATA3 was detected in the protein complex co-precipitated with livin antibody, and livin was also detected in the protein complex co-precipitated by GATA3 antibody. Conclusion Livin increases the expression of IL-4 and facilitates naive CD4 + T cells to differentiate into Th2 cells, which triggers airway allergy.

Food resources for Spoon-billed Sandpipers (Calidris pygmaea) in the mudflats of Leizhou Bay, southern China - Xiuyuan Lu; Hongyan Yang; Theunis Piersma; Lili Sun; Qing Chen; Yifei Jia; Guangchun Lei; Li Cheng; Xinpeng Rao (Frontiers in Marine Science, 2022)
Leizhou Bay in Guangdong Province is the most important wintering site in China for the critically endangered Spoon-billed Sandpipers ( Calidris pygmaea ). As food is usually a strong predictor of presence, in the winters of 2019-2022 we studied arthropod food resources and diet on the intertidal mudflats at the Tujiao and Hebei mudflats in Leizhou Bay. In December 2020, using a sampling device that encloses mobile epibenthic prey before the human sampler would disturb them in shallow pools, we visited 34 stations in their core foraging area at Tujiao. A total of 15 mobile benthic species were identified, including 13 arthropod and 2 fish species, with a total density of 106 animals/m 2 (range= 0.2-48 animals/m 2 ), with the lengths of the animals ranging from 1-19 mm. Two amphipod and one cumacean species contributed 85%. On the basis of photographs of foraging during low tide in 2019-2022, the visibly ingested prey items appeared to mainly consist of small shrimp, but also included crabs and fish. At 27 mm (compared with the 22 mm long bill of Spoon-billed Sandpipers) the average visibly ingested prey showed a strong size bias. Among the measured environmental covarying factors (sediment pH, salinity, TOC content, median particle size and distance from the seawall etc.) potentiually affecting the mobile epibenthic prey in shallow pools, only distance from the seawall was significantly and negatively correlated. Densities were higher within 1 km of the seawall (126 animals/m 2 ) than further offshore (69 animals/m 2 ). This may relate to the mangrove forests growing in abundance near the seawall providing released minerals, nutrients, bacterial production and diatoms for the benthic community in the adjacent mudflats. However, the potential negative impact of artificial mangrove expansion in Leizhou mudflats need to be carefully monitored and assessed to balance both mangrove and Spoon-billed Sandpipers conservation.

Temporal specificity of IL-6 knockout in enhancing the thermogenic capability of brown adipose tissue - Mei Dong; Cheng Gao; Yanxin Jia; Weijia Xu; Yan Liu; Xin Wen; Qingxin Liu; Hai Lin; Haifang Li (Journal of Physiology and Biochemistry, 2022)

Selection and identification of a specific peptide binding to ovarian cancer cells from a phage-displayed peptide library - Qian Gao; Lirong Chen; Chenshuang Jia; Yue Yuan; Xinyao Li; Zheng Lu; Yang Feng; Ruixia Zhao; Xuewei Zhao; Yiwen Wang; Sinan Cheng; Caixia Zhang; et al. (Biotechnology Letters, 2022)

Assessing the joint effects of brain aging and gut microbiota on the risks of psychiatric disorders - Huijie Zhang; Li Liu; Shiqiang Cheng; Yumeng Jia; Yan Wen; Xuena Yang; Peilin Meng; Chun’e Li; Chuyu Pan; Yujing Chen; Zhen Zhang; Jingxi Zhang; et al. (Brain Imaging and Behavior, 2022)

Short-term effect of sulfur dioxide (SO2) change on the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China: the first multi-city study to explore differences in occupational patients - Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Ying-Qing Li; Xin Cheng; Zhen-Hua Li; Yi-Cheng Mao; Cheng-Yang Hu; Kai Huang; Kun Ding; et al. (Environmental Science and Pollution Research, 2022)

Role of mountains and rivers in the formation of logistics enterprises’ spatial pattern in the central urban areas of Chongqing - Si-jing Liu; Cheng-jia Zhu; Nan-nan He; Guo-qi Li (Journal of Mountain Science, 2022)

The effect of meteorological drought on vegetation cover in the Yellow River basin, China - Lu Jia; Kun‐xia Yu; Zhan‐bin Li; Peng Li; Guo‐ce Xu; Yu‐ting Cheng; Xiang Zhang; Zhi Yang (International Journal of Climatology, 2022)
As a widespread natural disaster, drought has a significant impact on changes in regional vegetation cover. Based on 1‐month standardized precipitation index (SPI1), this study took the Yellow River basin (YRB) with frequent droughts as the research object, using NDVI data from 1999 to 2018, Mann–Kendall trend test, and correlation test to study the temporal and spatial characteristics of meteorological drought, explored the response of vegetation cover to meteorological drought, and further discussed the possible factors affecting meteorological drought. The results of the study showed that from 1999 to 2018, the SPI1 in the YRB had not increased significantly in a large area in different months ( p > .05). On the monthly time scale, the NDVI of the YRB gradually increased from north to south, showing a significant increasing trend the central area ( p p p

Modified effects of air pollutants on the relationship between temperature variability and hand, foot, and mouth disease in Zibo City, China - Chunyu Li; Yuchen Zhu; Kaili She; Yan Jia; Tingxuan Liu; Chuang Han; Qidi Fang; Chuanlong Cheng; Luyi Han; Ying Liu; Ying Zhang; Xiujun Li (Environmental Science and Pollution Research, 2022)

Limit state analysis of stepped sliding of jointed rock slope based on tensile-shear composite failure mode of rock bridges - Dejian Li; Wentao Jia; Xiao Cheng; Lianheng Zhao; Yingbin Zhang; Pengcheng Yu (Bulletin of Engineering Geology and the Environment, 2022)

Quinoline, with the active site of 8‐hydroxyl, efficiently inhibits Micropterus salmoides rhabdovirus (MSRV) infection in vitro and in vivo - Bo‐Yang Li; Fei Yang; Zhong‐Yu Zhang; Yu‐Feng Shen; Tao Wang; Liang Zhao; Jia‐Cheng Qin; Fei Ling; Gao‐Xue Wang (Journal of Fish Diseases, 2022)
Micropterus salmoides rhabdovirus (MSRV) is an significant pathogen that causes high mortality and related economic losses in bass aquaculture. There is no effective or approved therapy to date. In this study, we evaluated the anti‐MSRV effects of 22 quinoline derivatives in grass carp ovary (GCO) cells. Among these compounds, 8‐hydroxyquinoline exhibited valid inhibition in decreasing MSRV nucleoprotein gene expression levels of 99.3% with a half‐maximal inhibitory concentrations (IC 50 ) value of 4.66 μM at 48 h. Moreover, 8‐hydroxyquinoline significantly enhanced a protective effect in GCO cells by reducing the cytopathic effect (CPE). By comparing the anti‐MSRV activity of 22 quinoline derivatives, we found that 8‐hydroxyquinoline possessed the efficient active site of 8‐hydroxyl and inhibited MSRV infection in vitro. For in vivo studies, 8‐hydroxyquinoline via intraperitoneal injection exhibited an antiviral effect in MSRV‐infected largemouth bass by substantially enhancing the survival rate by 15.0%. Importantly, the viral loads in the infected largemouth bass notably reduced in the spleen on the third days post‐infection. Overall, 8‐hydroxyquinoline was considered to be an efficient agent against MSRV in aquaculture.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Quantitative detection of parasitic ciliate Cryptocaryon irritans in seawater with an optimized sample processing method - Jia‐Jia Tang; Zhi‐Hong Zhong; Zhi‐Cheng Li; Qing‐Kai Guo; Shi‐Yu Li; Yi‐Xuan Guo; Biao Jiang; An‐Xing Li (Journal of Fish Diseases, 2022)
The protozoan Cryptocaryon irritans is one of the most important ectoparasites of marine fish, causing ‘white spot disease’ and mass mortality in aquaculture. To accurately predict disease outbreaks and develop prevention strategies, improved detection methods are required that are sensitive, convenient and rapid. In this study, a pair of specific primers based on the C . irritans 18S rRNA gene was developed and used in a real‐time PCR (qPCR) assay. This assay was able to detect five theronts in 1 L of natural seawater. Furthermore, a linear model was established to analyse the log of Ct value and parasite abundance in seawater (y = –2.9623x + 24.2930), and the coefficient of determination (R 2 ) value was 0.979. A lysis buffer was optimized for theront DNA extraction and used for storage sample. This method was superior to the commercial water DNA kit, and there was no significant degradation of DNA at room temperature for 24–96 hr. A dilution method was developed to manage qPCR inhibitors and used to investigate natural seawater samples in a net cage farm with diseased fish, and the findings were consistent with the actual situation. This study provides a valuable tool for assisting in the early monitoring and control of cryptocaryoniasis in aquaculture.

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Fine mapping KT1 on wheat chromosome 5A that conditions kernel dimensions and grain weight - Zhongxin Kong; Ruiru Cheng; Haisheng Yan; Haiyun Yuan; Yong Zhang; Guoqiang Li; Haiyan Jia; Shulin Xue; Wenling Zhai; Yang Yuan; Zhengqiang Ma (Theoretical and Applied Genetics, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Determinants of soil carbon- and nitrogen-hydrolyzing enzymes within different afforested lands in central China - Qianxi Li; Yiran Dong; Qian Zhang; Wei Jia; Xiaoli Cheng (Environmental Science and Pollution Research, 2022)

Load transfer laws of tensile anchors in rock masses with weak interlayers based on a shear-slipping updating model - Yan Wang; Xin Xiang; Chang-dong Li; Guo-qiang Zhu; Cheng-bin Song; Jin-ye Xian; Jia-jun Zhang (Journal of Mountain Science, 2022)

Identification and characterization of microRNAs involved in double-color formation in Paeonia suffruticosa ‘Shima Nishiki’ by high-throughput sequencing - Xinpeng Zhang; Jinshan Jia; Mingyuan Zhao; Cheng Li; Xu Han; Zongda Xu (Horticulture, Environment, and Biotechnology, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Different changes in pre- and postsynaptic components in the hippocampal CA1 subfield after transient global cerebral ischemia - Yan Zhang; Bai-Hong Tan; Shuang Wu; Cheng-Hao Wu; Jia-Le Suo; Yue Gui; Cheng-Mei Zhou; Yan-Chao Li (Brain Structure and Function, 2022)

GC–MS fingerprints of essential oils from agarwood grown in wild and artificial environments - Cheng-piao Tian; Xing-dong Yao; Jia-hao Lu; Li-qun Shen; Ai-qun Wu (Trees, 2021)

Demographics of Scomberomorus commerson in the Central Taiwan Strait - Jinn-Shing Weng; Li-Chi Cheng; Yun-Sin Lo; Jen-Chieh Shiao; Jia-Sin He; Ming-An Lee; Kwang-Ming Liu (Journal of Marine Science and Engineering, 2021)
The narrow-barred Spanish mackerel Scomberomorus commerson is an economically essential species; however, few studies have investigated its demographic structure in the northwestern Pacific, which includes Taiwan’s waters. This study examined the growth parameters, age composition, mortality, and sex ratio of S. commerson catches by examining sagittal otoliths and other biological data collected in a 3-year project from June 2018 to June 2021. The transverse sections of sagittal otoliths exhibited alternating translucent and opaque zones, in annual cycles, and this observation was validated by otolith edge analysis. Opaque zones began to form in October; the growth peaked in December and lasted until March. Growth parameters were estimated for female (L∞ = 144.1 cm fork length [FL], k = 0.39 y−1, to = −0.85 y) and male (L∞ = 136.0 cm FL, k = 0.32 y−1, to = −1.49 y) specimens. The maximum recorded FL, body weight, and age were 159.0 cm, 27 kg, and 9.2 y for female and 135.0 cm, 17.8 kg, and 7.2 y for male specimens. Rapid growth was observed for both sexes, with FL reaching 66.8 ± 14.2 cm in female specimens and 70.1 ± 11.0 cm in male specimens during the first year of life. An age–length key based on the direct otolith aging and FL dataset (N = 646) was used to estimate the age composition of 3-year catches measured at landing (N = 16,133). The results verified that the S. commerson currently caught in the central Taiwan Strait are mainly young fish aged 1+ to 2+ y. The estimated fishing mortality (0.27 y−1) and exploitation rate (0.30) suggested that overfishing was not occurring in this stock. The findings of this study have helped clarify the population dynamics of the S. commerson in the Taiwan Strait, and the biological parameters reported herein can aid the management and conservation to ensure the sustainability of this species in this region.

Analysis on the risk of respiratory virus transmission by air conditioning system operation based on experimental evidence - Yonghong Jia; Yue Xiang; Shurui Guo; Lei Guo; Luyao Guo; Zhu Cheng; Yin Zhang; Li Zhang; Enshen Long (Environmental Science and Pollution Research, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

A small attentional YOLO model for landslide detection from satellite remote sensing images - Libo Cheng; Jia Li; Ping Duan; Mingguo Wang (Landslides, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Selection and optimum fertilization of Betula platyphylla hybrid clones for growth - Shuyuan Song; Siqi Cheng; Zhen Jia; Minghui Li; Jiabao Ji; Yifan Yang; Chu Wang; Chenrui Gu; Qibin Yu; Yuhui Weng; Guifeng Liu (Trees, 2021)

Dietary berberine can ameliorate glucose metabolism disorder of Megalobrama amblycephala exposed to a high-carbohydrate diet - Chang He; Xiaoyan Jia; Li Zhang; Fan Gao; Weibo Jiang; Chuang Wen; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Haifeng Mi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Assessing the Influence of Aerosol on Radiation and Its Roles in Planetary Boundary Layer Development - Zhigang Cheng; Yubing Pan; Ju Li; Xingcan Jia; Xinyu Zhang; Pengkun Ma; Qianqian Wang; Junxia Dou; Jingjiang Zhang; Jiannong Quan (Journal of Meteorological Research, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

A spatial-spectral clustering-based algorithm for endmember extraction and hyperspectral unmixing - Xiaoyu Cheng; Zhouyin Cai; Jia Li; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Effect on intestinal microbiota, bioaccumulation, and oxidative stress of Carassius auratus gibelio under waterborne cadmium exposure - Nan Wang; Zhengyao Guo; Yilin Zhang; Peijun Zhang; Jia Liu; Yi Cheng; Lei Zhang; Yuehong Li (Fish Physiology and Biochemistry, 2020)

The Bre1/Rad6 machinery: writing the central histone ubiquitin mark on H2B and beyond - Zhi-Heng Deng; Hua-Song Ai; Cheng-Piao Lu; Jia-Bin Li (Chromosome Research, 2020)

Chemical constituents from common vetch ( Vicia sativa L.) and their antioxidant and cytotoxic activities - Li-Fang Liu; Wen-Hai Li; Man-Yu Li; Xiao-Zhen Wu; Fan Yang; Jia-Nan Xu; Cheng-Shan Yuan (Natural Product Research, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Identification and Characterization of the Nuclease Activity of the Extracellular Proteins from Salmonella enterica Serovar Typhimurium - Chengshui Liao; Mengke Zhang; Xiangchao Cheng; Qi Li; Fuchao Mao; Xiaoli Wang; Chuan Yu; Zuhua Yu; Yanyan Jia; Jing Li; Lei He; Chunjie Zhang; et al. (Current Microbiology, 2020)

A Comparative Study of Associated Microbiota Between Pig Farm and Pig Slaughterhouse in Guangdong, China - Jian-Yong Wu; Yan-Shan Zhu; Cheng Guo; Yao Xia; Zhong-Min Guo; Qian-Lin Li; Jia-Hai Lu (Current Microbiology, 2020)

Molecular Mobility and Crystal Growth in Amorphous Binary Drug Delivery Systems: Effects of Low-Concentration Poly(Ethylene Oxide) - Qin Shi; Jin Cheng; Fang Li; Jia Xu; Chen Zhang (AAPS PharmSciTech, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Five new ent -kaurane diterpenes from Annona squamosa L. pericarps - Ya-Yun Chen; Cheng-Yao Ma; Mao-Lin Wang; Jia-Hui Lu; Peng Hu; Jian-Wei Chen; Xiang Li; Yong Chen (Natural Product Research, 2020)

Genetic architecture of leaf morphological and physiological traits in a Populus deltoides ‘Danhong’ × P. simonii ‘Tongliao1’ pedigree revealed by quantitative trait locus analysis - Pei Sun; Huixia Jia; Xingqi Cheng; Yahong Zhang; Jianbo Li; Lei Zhang; Mengzhu Lu; Jin Zhang; Jianjun Hu (Tree Genetics & Genomes, 2020)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

Review of drought impacts on carbon cycling in grassland ecosystems - Tianjie Lei; Jie Feng; Cuiying Zheng; Shuguang Li; Yang Wang; Zhitao Wu; Jingxuan Lu; Guangyuan Kan; Changliang Shao; Jinsheng Jia; Hui Cheng (Frontiers of Earth Science, 2020)

Time-resolved black carbon aerosol vertical distribution measurements using a 356-m meteorological tower in Shenzhen - Tianlin Sun; Cheng Wu; Dui Wu; Ben Liu; Jia Yin Sun; Xia Mao; Honglong Yang; Tao Deng; Lang Song; Mei Li; Yong Jie Li; Zhen Zhou (Theoretical and Applied Climatology, 2020)
Black carbon (BC) is an essential climate forcer in the atmosphere. Large uncertainties remain in BC’s radiative forcing estimation by models, partially due to the limited measurements of BC vertical distributions near the surface layer. We conducted time-resolved vertical profiling of BC using a 356-m meteorological tower in Shenzhen, China. Five micro-aethalometers were deployed at different heights (2, 50, 100, 200, and 350 m) to explore the temporal dynamics of BC vertical profile in the highly urbanized areas. During the observation period (December 6–15, 2017), the average equivalent BC (eBC) concentrations were 6.6 ± 3.6, 5.4 ± 3.3, 5.9 ± 2.8, 5.2 ± 1.8, and 4.9 ± 1.4 μg m −3 , from 2 to 350 m, respectively. eBC temporal variations at different heights were well correlated. eBC concentrations generally decreased with height. At all five heights, eBC diurnal variations exhibited a bimodal pattern, with peaks appearing at 09:00–10:00 and 19:00–21:00. The magnitudes of these diurnal peaks decreased with height, and the decrease was more pronounced for the evening peak. eBC episodes were largely initiated by low wind speeds, implying that wind speed played a key role in the observed eBC concentrations. eBC wind-rose analysis suggested that elevated eBC events at different heights originate from different directions, which suggested contributions from local primary emission plumes. Air masses from central China exhibited much higher eBC levels than the other three backward trajectory clusters found herein. The absorption Ångström exponent (AAE 375–880 ) showed clear diurnal variations at 350 m and increased slightly with height.

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Biocontrol potential of Bacillus subtilis IBFCBF-4 against Fusarium wilt of watermelon - Jiuxiang Zhu; Taimeng Tan; Airong Shen; Xiebin Yang; Yongting Yu; Chunsheng Gao; Zhimin Li; Yi Cheng; Jia Chen; Litao Guo; Xiangping Sun; Zhun Yan; et al. (Journal of Plant Pathology, 2020)

Transcriptome analysis revealed cadmium accumulation mechanisms in hyperaccumulator Siegesbeckia orientalis L. - Xiaoxun Xu; Shirong Zhang; Zhang Cheng; Ting Li; Yongxia Jia; Guiyin Wang; Zhanbiao Yang; Junren Xian; Yuanxiang Yang; Wei Zhou (Environmental Science and Pollution Research, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Dynamic change of vegetation and its response to climate and topographic factors in the Xijiang River basin, China - Lu Jia; Zhan-bin Li; Guo-ce Xu; Zong-ping Ren; Peng Li; Yu-ting Cheng; Yi-xin Zhang; Bin Wang; Jia-xin Zhang; Shu Yu (Environmental Science and Pollution Research, 2020)

Integrity monitoring of carrier phase-based ephemeris fault detection - Liang Li; Xiaosong Liu; Chun Jia; Chun Cheng; Jiaxiang Li; Lin Zhao (GPS Solutions, 2020)

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

v301, a new allele of BRITTLE CULM 12, and its regulation of the early senescence of the leaf blade in rice - Ji-le Ni; Xiao-zhu Wen; Cheng-bing Tang; Wei-jiang Tian; Wen-jing Yang; Jia Xie; Xiao-bo Zhang; Yang-yang Li; Yu-zhen Xiong; Ying Sun; Zhu Zhu; Ying Wang; et al. (Acta Physiologiae Plantarum, 2020)

Tibial growth plate vascularization is inhibited by the dithiocarbamate pesticide thiram in chickens: potential relationship to peripheral platelet counts alteration - Shu-Cheng Huang; Lei Li; Mujeeb Ur Rehman; Jin-dong Gao; Li-hong Zhang; Xiao-le Tong; Muhammad Waqas; Jia-kui Li (Environmental Science and Pollution Research, 2019)

Purification and characterization of an endo-xylanase from Trichoderma sp., with xylobiose as the main product from xylan hydrolysis - Li-Hao Fu; Nan Jiang; Cheng-Xi Li; Xue-Mei Luo; Shuai Zhao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2019)

Influences of hydrate decomposition on submarine landslide - Benjian Song; Yuanfang Cheng; Chuanliang Yan; Zhongying Han; Jiping Ding; Yang Li; Jia Wei (Landslides, 2019)

FadP affects the virulence of Ralstonia pseudosolanacearum by altering nitrogen metabolism processes and reducing motility, cellulase, and extracellular polysaccharide production - Jia-chun Wu; Min Zhong; Xing-wei Li; Cheng-peng Yu; Qiong-guang Liu (Journal of Plant Pathology, 2019)

Selection of reference genes for miRNA quantitative PCR and its application in miR-34a/Sirtuin-1 mediated energy metabolism in Megalobrama amblycephala - Jie Liu; Erteng Jia; Huajuan Shi; Xiangfei Li; Guangzhen Jiang; Cheng Chi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2019)

Identification of SNP markers linked to the weeping trait in Prunus mume - Suzhen Li; Tangchun Zheng; Xiaokang Zhuo; Lulu Li; Like Qiu; Jia Wang; Tangren Cheng; Qixiang Zhang (Euphytica, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Yang-Shuo Tang; Yan-Hua Zhao; Yong Zhong; Xiao-Zhao Li; Jia-Xi Pu; Yan-Cheng Luo; Qiao-Ling Zhou (Inflammation Research, 2019)

Molecular characterization and expression analysis of cyp19a gene in Culter alburnus - Jianbo Zheng; Yongyi Jia; Fei Li; Shili Liu; Meili Chi; Shun Cheng; Zhimi Gu (Fisheries Science, 2019)

Synthesis of oleanolic acid/ursolic acid/glycyrrhetinic acid-hydrogen sulfide donor hybrids and their antitumor activity - Li-xin Sheng; Jia-yan Huang; Chun-mei Liu; Ju-zheng Zhang; Ke-guang Cheng (Medicinal Chemistry Research, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

Tolerance of two apple rootstocks to short-term salt stress: focus on chlorophyll degradation, photosynthesis, hormone and leaf ultrastructures - Yan-fang Zhu; Yu-xia Wu; Ya Hu; Xu-mei Jia; Tong Zhao; Li Cheng; Yan-xiu Wang (Acta Physiologiae Plantarum, 2019)

Giant Submarine Landslide in the South China Sea: Evidence, Causes, and Implications - Chaoqi Zhu; Sheng Cheng; Qingping Li; Hongxian Shan; Jing’an Lu; Zhicong Shen; Xiaolei Liu; Yonggang Jia (Journal of Marine Science and Engineering, 2019)
Submarine landslides can be tremendous in scale. They are one of the most important processes for global sediment fluxes and tsunami generation. However, studies of prodigious submarine landslides remain insufficient. In this review paper, we compile, summarize, and reanalyze the results of previous studies. Based on this reanalysis, we discover the giant Baiyun–Liwan submarine slide in the Pearl River Mouth Basin, South China Sea. We describe three concurrent pieces of evidence from ~23 Ma to 24 Ma, the Oligocene–Miocene boundary, for this landslide: the shoreward shift of the shelf break in the Baiyun Sag, the slump deposition to the southeast, and the abrupt decrease in the accumulation rate on the lower continental slope. This landslide extends for over 250 km, and the total affected area of the slide is up to ~35,000–40,000 km2. The scale of the landslide is similar to that of the Storegga slide, which has long been considered to be the largest landslide on earth. We suggest that strike–slip movement along the Red River Fault and ridge jump of the South China Sea caused the coeval Baiyun–Liwan submarine slide. The identification of the giant landslide will promote the understanding of not only its associated geohazards but also the steep rise of the Himalayan orogeny and marine engineering. More attention needs to be paid to areas with repeated submarine landslides and offshore installations.

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Development of Upwelling during the Sedimentary Period of the Organic-Rich Shales in the Wufeng and Longmaxi Formations of the Upper Yangtze Region and Its Impact on Organic Matter Enrichment - Shao-Ze Zhao; Yong Li; Hua-Jun Min; Tong Wang; Zhou Nie; Zhan-Zhao Zhao; Jia-Zhen Qi; Jin-Cheng Wang; Jia-Peng Wu (Journal of Marine Science and Engineering, 2019)
This study uses logging data, mineral component content, total organic carbon (TOC) content, and microscopic characteristics of the organic-rich shales in the Wufeng and Longmaxi Formations, as well as data reported by other researchers, to demonstrate that upwelling has played an important role in the organic matter enrichment. The results show that (1) the organic-rich shales of Well N211 in the Upper Yangtze region are located in the Wufeng Formation and the lower Longmaxi Formation, with a burial depth between 2308–2357 m. (2) The organic-rich shales are enriched in biogenic silica. (3) Based on paleogeographic location and characteristics of organisms, this study determines that upwelling occurred during the deposition of the organic-rich shales in the Wufeng and Longmaxi Formations, promoting the enrichment of organic matter in the shales. (4) The upwelling intensity gradually increased from the sedimentary period of the organic-rich shales in the mid-lower Wufeng Formation to the sedimentary period of the Guanyinqiao Member, and then decreased gradually from the sedimentary period of the Guanyinqiao Member to the sedimentary period of the organic-rich shales in the Longmaxi Formation, and leads to the different enrichment of organic matter in the vertical direction. The different developments of upwelling led to the coexistence of both high and low TOC contents in the Guanyinqiao Member along the vertical direction.

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Impact of phosphate additive on organic carbon component degradation during pig manure composting - Juan Wu; Aiguo Zhang; Guoxue Li; Yuquan Wei; Fuya Jia; Ying Liang; Yandong Cheng; Yan Liu (Environmental Science and Pollution Research, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

cAMP Receptor Protein of Salmonella enterica Serovar Typhimurium Modulate Glycolysis in Macrophages to Induce Cell Apoptosis - Ke Ding; Chunjie Zhang; Jing Li; Songbiao Chen; Chengshui Liao; Xiangchao Cheng; Chuang Yu; Zuhua Yu; Yanyan Jia (Current Microbiology, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Transcriptome analysis in Malus halliana roots in response to iron deficiency reveals insight into sugar regulation - Ya Hu; Yan-fang Zhu; Ai-xia Guo; Xu-mei Jia; Li Cheng; Tong Zhao; Yan-xiu Wang (Molecular Genetics and Genomics, 2018)

Association mapping and favourable QTL alleles for fibre quality traits in Upland cotton (Gossypium hirsutum L.) - Cheng-Guang Dong; Juan Wang; Yu Yu; Bao-Cheng Li; Quan-Jia Chen (Journal of Genetics, 2018)

Hazard zoning of trunk highway slope disasters: a case study in northern Shaanxi, China - Huan Zhao; Wei-Ping Tian; Jia-chun Li; Bao-Cheng Ma (Bulletin of Engineering Geology and the Environment, 2018)

Long runout mechanism of the Shenzhen 2015 landslide: insights from a two-phase flow viewpoint - Cheng Qiao; Guo-qiang Ou; Hua-li Pan; Chao-jun Ouyang; Yang Jia (Journal of Mountain Science, 2018)

Relationship Between the Microstructure/Pore Structure of Oil-Well Cement and Hydrostatic Pressure - Kaiqiang Liu; Xiaowei Cheng; Xingguo Zhang; Zaoyuan Li; Jia Zhuang; Xiaoyang Guo (Transport in Porous Media, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

Developmental transcriptome analysis of floral transition in Rosa odorata var. gigantea - Xuelian Guo; Chao Yu; Le Luo; Huihua Wan; Ni Zhen; Yushu Li; Tangren Cheng; Jia Wang; Huitang Pan; Qixiang Zhang (Plant Molecular Biology, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

Bacterial community structure and abundances of antibiotic resistance genes in heavy metals contaminated agricultural soil - Fengli Zhang; Xiaoxue Zhao; Qingbo Li; Jia Liu; Jizhe Ding; Huiying Wu; Zongsheng Zhao; Yue Ba; Xuemin Cheng; Liuxin Cui; Hongping Li; Jingyuan Zhu (Environmental Science and Pollution Research, 2018)

Position-domain integrity risk-based ambiguity validation for the integer bootstrap estimator - Liang Li; Haodong Shi; Chun Jia; Jianhua Cheng; Hui Li; Lin Zhao (GPS Solutions, 2018)

A novel Scan SAR imaging method for maritime surveillance via L p regularization - Jia-cheng Ni; Qun Zhang; Yu-fu Yin; Ying Luo; Li Sun (International Journal of Remote Sensing, 2018)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Modulation of financial deprivation on deception and its neural correlates - Peng Sun; Xiaoli Ling; Li Zheng; Jia Chen; Lin Li; Zhiyuan Liu; Xuemei Cheng; Xiuyan Guo (Experimental Brain Research, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Histological analysis and identification of spermatogenesis-related genes in 2-, 6-, and 12-month-old sheep testes - Man Bai; Limin Sun; Jia Zhao; Lujie Xiang; Xiaoyin Cheng; Jiarong Li; Chao Jia; Huaizhi Jiang (The Science of Nature, 2017)

Deletion of TpKu70 facilitates gene targeting in Talaromyces pinophilus and identification of TpAmyR involvement in amylase production - Ting Zhang; Shuai Zhao; Lu-Sheng Liao; Cheng-Xi Li; Gui-Yan Liao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Mutations in IL36RN are associated with geographic tongue - Jianying Liang; Peichen Huang; Huaguo Li; Jia Zhang; Cheng Ni; Yirong Wang; Jinwen Shen; Chunxiao Li; Lu Kang; Jie Chen; Hui Zhang; Zhen Wang; et al. (Human Genetics, 2017)

Young Seedling Stripe1 encodes a chloroplast nucleoid-associated protein required for chloroplast development in rice seedlings - Kunneng Zhou; Yulong Ren; Feng Zhou; Ying Wang; Long Zhang; Jia Lyu; Yihua Wang; Shaolu Zhao; Weiwei Ma; Huan Zhang; Liwei Wang; Chunming Wang; et al. (Planta, 2017)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

Map-based cloning, identification and characterization of the w gene controlling white immature fruit color in cucumber (Cucumis sativus L.) - Hanqiang Liu; Jianqing Jiao; Xinjing Liang; Jia Liu; Huanwen Meng; Shuxia Chen; Yuhong Li; Zhihui Cheng (Theoretical and Applied Genetics, 2016)

Polypore diversity in North America with an annotated checklist - Li-Wei Zhou; Karen K. Nakasone; Harold H. Burdsall; James Ginns; Josef Vlasák; Otto Miettinen; Viacheslav Spirin; Tuomo Niemelä; Hai-Sheng Yuan; Shuang-Hui He; Bao-Kai Cui; Jia-Hui Xing; et al. (Mycological Progress, 2016)

Plasma Homocysteine Levels Predict the Risk of Acute Cerebral Infarction in Patients with Carotid Artery Lesions - Wei Wu; Yi Guan; Kan Xu; Xi-Jia Fu; Xiao-Feng Lei; Li-Jian Lei; Zhi-Qing Zhang; Yan Cheng; Yun-Qian Li (Molecular Neurobiology, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Geographic distribution of archaeological sites and their response to climate and environmental change between 10.0–2.8 ka BP in the Poyang Lake Basin, China - Jiajia Xu; Yulian Jia; Chunmei Ma; Cheng Zhu; Li Wu; Yuyuan Li; Xinhao Wang (Journal of Geographical Sciences, 2016)

Feeding ecology of the mud shrimp S olenocera melantho in the E ast C hina S ea - Hui Yu Li; Jian Zhong Ling; Li Ping Yan; Jia Hua Cheng; Fen Hu (Marine Ecology, 2016)
The feeding habits of the mud shrimp Solenocera melantho were studied in the East China Sea by analysing 720 stomach contents and comparing diet composition and prey diversity among seasons, sexes and size classes. Feeding activity was linked to season and ovarian condition. The stomach fullness was high during spring and summer and low in fall. Females with advanced ovaries also displayed low stomach fullness, which suggests that feeding activity is affected by the reproductive cycle. The diet of S. melantho consisted of 42 different prey categories, primarily smaller crustaceans, Foraminifera, polychaetes, mollusks and fishes (larvae and eggs). Crustacea,Foraminifera and polychaetes together constituted the dominant prey groups, accounting for 75% of total prey abundance and >50% of total prey occurrence. Diet composition differed among seasons between sexes and size classes. Females and males consumed the same prey items but with different orders of importance. In terms of body size, the small shrimps preferred relatively small food items, such as Foraminifera and algae, whereas larger shrimps preferred polychaetes and crustaceans. Trophic diversity varied among the seasons within both sexes and size classes, with the highest values being observed in fall. Niche overlap was high within both sexes and size classes among seasons (0.6051–0.8740).

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

Isolation and structural elucidation of a novel homogenous polysaccharide from Tricholoma matsutake - Hua Cheng; Yan Jia; Ling Wang; Xiaoying Liu; Guangrong Liu; Li Li; Congfen He (Natural Product Research, 2016)

proBDNF Attenuates Hippocampal Neurogenesis and Induces Learning and Memory Deficits in Aged Mice - Jia Chen; Cheng-Ren Li; Heng Yang; Juan Liu; Tao Zhang; Shu-Sheng Jiao; Yan-Jiang Wang; Zhi-Qiang Xu (Neurotoxicity Research, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Experimental studies on the Danxia landscape morphogenesis in Mt. Danxiashan, South China - Cheng Zhu; Li Wu; Tongxin Zhu; Rongfeng Hou; Zhinong Hu; Yan Tan; Wei Sun; Tianjiao Jia; Hua Peng (Journal of Geographical Sciences, 2015)

Spatiotemporal variation of riverine nutrients in a typical hilly watershed in southeast China using multivariate statistics tools - Xiao-fei Nie; Heng-peng Li; Jia-hu Jiang; Ya-qin Diao; Peng-cheng Li (Journal of Mountain Science, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

Effects of heat stress on serum insulin, adipokines, AMP-activated protein kinase, and heat shock signal molecules in dairy cows - Li Min; Jian-bo Cheng; Bao-lu Shi; Hong-jian Yang; Nan Zheng; Jia-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Expression of Cyclooxygenase-2 in Squamous Cell Carcinoma and Keratoacanthoma and its Clinical Significance - Hai-Kang Hua; Cheng Jin; Li-Jia Yang; Shi-Qin Tao; Xiao-Hong Zhu (Cell Biochemistry and Biophysics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Geissoschizine methyl ether N -oxide, a new alkaloid with antiacetylcholinesterase activity from Uncaria rhynchophylla - Wei-Wei Jiang; Jia Su; Xing-De Wu; Juan He; Li-Yan Peng; Xiao Cheng; Qin-Shi Zhao (Natural Product Research, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

In vitro simulation of in vivo pharmacokinetic model with intravenous administration via flow rate modulation - Yuan-cheng Chen; Wang Liang; Jia-li Hu; Gao-li He; Xiao-jie Wu; Xiao-fang Liu; Jing Zhang; Xue-qian Hu (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Effects of dominant microalgae species and bacterial quantity on shrimp production in the final culture season - Yu-cheng Cao; Guo-liang Wen; Zhuo-jia Li; Xiao-zhu Liu; Xiao-juan Hu; Jia-song Zhang; Jian-guo He (Journal of Applied Phycology, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Ectopic expression of RBP4 impairs the insulin pathway and inguinal fat deposition in mice - Jia Cheng; Yuefeng Li; Guofang Wu; Jiameng Zheng; Hongzhao Lu; Xin’e Shi; Gongshe Yang (Journal of Physiology and Biochemistry, 2014)

Sensitisation of ovarian cancer cells to cisplatin by flavonoids from Scutellaria barbata - Jie Li; Yun Wang; Jia-Chuan Lei; Yang Hao; Yuan Yang; Cheng-Xiong Yang; Jian-Qing Yu (Natural Product Research, 2014)

The activation of TLR7 regulates the expression of VEGF, TIMP1, MMP2, IL-6, and IL-15 in Hela cells - Lei Li; Feng-Wei Cheng; Fang Wang; Bo Jia; Xin Luo; Sheng-Quan Zhang (Molecular and Cellular Biochemistry, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Neuronal Oscillations in Golgi Cells and Purkinje Cells are Accompanied by Decreases in Shannon Information Entropy - Jian-Jia Huang; Cheng-Tung Yen; Hen-Wai Tsao; Meng-Li Tsai; Chiming Huang (The Cerebellum, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

The anti-adipogenic effect of PGRN on porcine preadipocytes involves ERK1,2 mediated PPARγ phosphorylation - Hao Yang; Jia Cheng; Ziyi Song; Xinjian Li; Zhenyu Zhang; Yin Mai; Weijun Pang; Xin’e Shi; Gongshe Yang (Molecular Biology Reports, 2013)

Gardiquimod inhibits the expression of calcium-induced differentiation markers in HaCaT cells - Bo Jia; Xin Luo; Feng-Wei Cheng; Lei Li; Dao-Jun Hu; Fang Wang; Sheng-Quan Zhang (Molecular Biology Reports, 2013)

Applications of 3D-QSAR and structure-based pharmacophore modeling, virtual screening, ADMET, and molecular docking of putative MAPKAP-K2 (MK2) inhibitors - Tai-Jin Wang; Lu Zhou; Jia Fei; Zi-Cheng Li; Lu-fen He (Medicinal Chemistry Research, 2013)

TAK1 inhibitor 5Z-7-oxozeaenol sensitizes neuroblastoma to chemotherapy - Yihui Fan; Jin Cheng; Sanjeev A. Vasudevan; Roma H. Patel; Li Liang; Xin Xu; Yanling Zhao; Wei Jia; Fengmin Lu; Hong Zhang; Jed G. Nuchtern; Eugene S. Kim; et al. (Apoptosis, 2013)

Enzymatic synthesis of glutathione using engineered Saccharomyces cerevisiae - Jia-li Chen; Liang Xie; Jing-jing Cai; Cheng-shuai Yang; Xue-hui Duan (Biotechnology Letters, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Effective inhibition of mRNA accumulation and protein expression of H5N1 avian influenza virus NS1 gene in vitro by small interfering RNAs - Hanwei Jiao; Li Du; Yongchang Hao; Ying Cheng; Jing Luo; Wenhua Kuang; Donglin Zhang; Ming Lei; Xiaoxiao Jia; Xiaoru Zhang; Chao Qi; Hongxuan He; et al. (Folia Microbiologica, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Artificial seed production and cultivation of the edible brown alga Sargassum naozhouense Tseng et Lu - En Yi Xie; Dong Chao Liu; Cheng Jia; Xiu Li Chen; Bin Yang (Journal of Applied Phycology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Expression of survivin and patients survival in non-small cell lung cancer: a meta-analysis of the published studies - Li-nian Huang; Dong-sheng Wang; Yu-qing Chen; Cheng-ling Zhao; Bei-lei Gong; An-bang Jiang; Wei Jia; Feng-dan Hu (Molecular Biology Reports, 2013)

Methylglyoxal Induces Tau Hyperphosphorylation via Promoting AGEs Formation - Xiao-Hong Li; Jia-Zhao Xie; Xia Jiang; Bing-Ling Lv; Xiang-Shu Cheng; Lai-Ling Du; Jia-Yu Zhang; Jian-Zhi Wang; Xin-Wen Zhou (NeuroMolecular Medicine, 2012)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

First record of wild ephyrae of the giant jellyfish Nemopilema nomurai - Masaya Toyokawa; Masashi Shibata; Jia-Hua Cheng; Hui-Yu Li; Jian-Zhong Ling; Nan Lin; Zun-Lei Liu; Yi Zhang; Manabu Shimizu; Hideki Akiyama (Fisheries Science, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Effect of groundwater geochemistry on pentachlorophenol remediation by smectite-templated nanosized Pd0/Fe0 - Hanzhong Jia; Cheng Gu; Hui Li; Xiaoyun Fan; Shouzhu Li; Chuanyi Wang (Environmental Science and Pollution Research, 2012)

Erratum to: Potent growth-inhibitory effect of TRAIL therapy mediated by double-regulated oncolytic adenovirus on osteosarcoma - Chunbao Li; Qianpeng Cheng; Jia Liu; Bin Wang; Dongfeng Chen; Yujie Liu (Molecular and Cellular Biochemistry, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Potent growth-inhibitory effect of TRAIL therapy mediated by double-regulated oncolytic adenovirus on osteosarcoma - Li Chunbao; Cheng Qianpeng; Liu Jia; Wang Bin; Chen Dongfeng; Liu Yujie (Molecular and Cellular Biochemistry, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Decontamination of Bacillus subtilis var. niger spores on selected surfaces by chlorine dioxide gas - Yan-ju Li; Neng Zhu; Hai-quan Jia; Jin-hui Wu; Ying Yi; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Significant genetic differentiation between native and introduced silver carp (Hypophthalmichthys molitrix) inferred from mtDNA analysis - Si-Fa Li; Jia-Wei Xu; Qi-Ling Yang; Cheng-Hui Wang; Duane C. Chapman; Guoqing Lu (Environmental Biology of Fishes, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Characteristics of strong earthquake evolution around the eastern boundary faults of the Sichuan-Yunnan rhombic block - Jia Cheng; Jie Liu; WeiJun Gan; HuaiZhong Yu; Gang Li (Science China Earth Sciences, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Angiotensin II Infusion–Induced Inflammation, Monocytic Fibroblast Precursor Infiltration, and Cardiac Fibrosis are Pressure Dependent - Guanming Qi; Lixin Jia; Yulin Li; Yunfei Bian; Jizhong Cheng; Huihua Li; Chuanshi Xiao; Jie Du (Cardiovascular Toxicology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Isolation of a 2-oxetanone from the fruits of Synsepalum dulcificum - Ming-Jen Cheng; Wen-Li Lo; Lee-Yu Huang; Chyi-Jia Wang; Chung-Yi Chen (Natural Product Research, 2010)

Epigenetic regulation of adipocyte differentiation and adipogenesis - Hong-xing Li; Lei Xiao; Cheng Wang; Jia-li Gao; Yong-gong Zhai (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and identification of a phosphate-solubilizing bacterium Pantoea stewartii subsp. stewartii g6, and effects of temperature, salinity, and pH on its growth under indoor culture conditions - Xiao-Juan Hu; Zhuo-Jia Li; Yu-Cheng Cao; Jun Zhang; Ying-Xue Gong; Yu-Feng Yang (Aquaculture International, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Genome relationships in the genus Dasypyrum: evidence from molecular phylogenetic analysis and in situ hybridization - Cheng Liu; Guang-Rong Li; Sunish Kumar Sehgal; Ju-Qing Jia; Zu-Jun Yang; Bernd Friebe; Bikram Gill (Plant Systematics and Evolution, 2010)

Biochemical characterization of the small ubiquitin-like modifiers of Chlamydomonas reinhardtii - Yung-Cheng Shin; Bang-Yu Liu; Jia-Yun Tsai; Jiunn-Tzong Wu; Li-Kwan Chang; Shih-Chung Chang (Planta, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Phylogenetic analyses of an isolate obtained from potato in 1985 revealed potato virus X was introduced to China via multiple events - Xiao-Qing Yu; Jin-Lei Jia; Cheng-Ling Zhang; Xiang-Dong Li; Yu-Jun Wang (Virus Genes, 2010)

Phenotypic and molecular characterization of two novel CTX-M enzymes carried by Klebsiella pneumoniae - Jun Cheng; Wei Gao; Jun Yin; Zhen Sun; Ying Ye; Yu-Feng Gao; Xu Li; Jia-Bin Li (Molecular Biology Reports, 2010)

Silencing induced by inverted repeat constructs in protoplasts of Nicotiana benthamiana - Ling Jiang; Jia Wang; Zhuo Liu; Li Wang; Fan Zhang; Guo-cheng Liu; Qi Zhong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Dissipation and Residues of Chlormequat in Wheat and Soil - Xing-li Guo; Chun-hong Jia; Er-cheng Zhao; Yan-jun Xu; Li-jun Han; Shu-ren Jiang (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Optimization of soybean (Glycine max (L.) Merrill) in planta ovary transformation using a linear minimal gus gene cassette - Ming Liu; Jun Yang; Yun-qing Cheng; Li-jia An (Journal of Zhejiang University-SCIENCE B, 2009)

In silico cloning and characterization of p8 homolog cDNA from common urchin (Paracentrotus lividus) - Jia-Qing Wang; Jin-Cheng Han; Dai-Zong Li; Lin-Chun Li (Molecular Biology Reports, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Isolation of a gene encoding endoglucanase activity from uncultured microorganisms in buffalo rumen - Li Liu; Yi Feng; Cheng-Jie Duan; Hao Pang; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2009)

A novel SHV-type β-lactamase variant (SHV-89) in clinical isolates in China - Jia-Bin Li; Jun Cheng; Qian Wang; Yan Chen; Ying Ye; Xue-Jun Zhang (Molecular Biology Reports, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Chromosomal aberrations and DNA damage in human populations exposed to the processing of electronics waste - Qiang Liu; Jia Cao; Ke Qiu Li; Xu Hong Miao; Guang Li; Fei Yue Fan; Yong Cheng Zhao (Environmental Science and Pollution Research, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Bioactive compounds of inhibiting xanthine oxidase from Selaginella labordei - Wen-Jie Tan; Jia-Cheng Xu; Li Li; Ke-Li Chen (Natural Product Research, 2009)

Effects of saltmarsh invasion by Spartina alterniflora on arthropod community structure and diets - Yu-Tong Wu; Cheng-Huan Wang; Xiao-Dong Zhang; Bin Zhao; Li-Fen Jiang; Jia-Kuan Chen; Bo Li (Biological Invasions, 2009)

Temporal expression of cyclooxygenase-2 in peritoneal macrophages of rats and effects of panax notoginseng saponins - Z. B. Yuan; H. G. Zhang; Y. Jia; Y. Q. Cheng; X. H. Li (Inflammation Research, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Characterization of a Novel AmpC-Type Plasmid-Mediated β-Lactamase from an Escherichia coli Strain Isolated in China - Qian Wang; Jun Cheng; Yan Chen; Ying Ye; Jia-Bin Li; Xue-Jun Zhang (Current Microbiology, 2008)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Litter pool sizes, decomposition, and nitrogen dynamics in Spartina alterniflora-invaded and native coastal marshlands of the Yangtze Estuary - Cheng Zhang Liao; Yi Qi Luo; Chang Ming Fang; Jia Kuan Chen; Bo Li (Oecologia, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Frequent loss of membranous E-cadherin in gastric cancers: A cross-talk with Wnt in determining the fate of β-catenin - Xiao-Xin Cheng; Zi-Chuang Wang; Xiao-Yan Chen; Yuan Sun; Qing-You Kong; Jia Liu; Xue Gao; Hong-Wei Guan; Hong Li (Clinical & Experimental Metastasis, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)